Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 103173460 species occurrences available in GBIF matching the query: { "and" : [ "BasisOfRecord is Specimen", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 103173460 records from 11497 constituent datasets: 78 records from Etnomicología en la Sierra de Santa Marta, Veracruz. 7 records from Genus Stathmopoda Herrich-Schäffer, 1853 (Lepidoptera: Stathmopodidae) from China: Descriptions of thirteen new species. 4 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 4 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 3 records from A new species of Auriculostoma (Trematoda: Allocreadiidae) from the intestine of Brycon guatemalensis (Characiformes: Bryconidae) from the Usumacinta River Basin, Mexico, based on morphology and 28 S rDNA sequences, with a key to species of the genus. 14 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 54 records from Anfibios y reptiles de la serranía las Quinchas, Boyacá - Proyecto Boyacá BIO. 18 records from New and rare micro-pagurid hermit crabs (Crustacea: Anomura: Paguridae) from the Caribbean Sea and Gulf of Mexico. 9 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 5 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 7 records from New species of ant-mimicking jumping spiders of the genus Myrmarachne MacLeay, 1839 (Araneae: Salticidae) from north Queensland, Australia. 2 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 8 records from Three new species of Aricidea (Acmira) (Annelida: Paraonidae) from the Continental Shelf of Eastern Brazil, Southwestern Atlantic. 20 records from Three new species of the primitively segmented spiders from Mt Yuelu, Hunan, China (Mesothelae, Liphistiidae). 9 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 96 records from Coleção de Nematoda do Museu Nacional - UFRJ. 1 records from A new species of Smicromorpha (Hymenoptera, Chalcididae) from Vietnam, with notes on the host association of the genus. 2 records from Description of a new species of deep-sea spider crab from the genus Crocydocinus Lee, Richer de Forges & Ng, 2019, from the south-eastern Arabian Sea (Crustacea Decapoda: Majoidea: Epialtidae). 32 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 14498 records from Lepidoptera (Rhopalocera y Heterocera) de áreas prioritarias para la conservación en la Península de Yucatán, con registros de adultos y estados inmaduros (Heterocera). 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 209233 records from Canadian Museum of Nature Herbarium. 700 records from Banco de Germoplasma del Real Jardín Botánico Juan Carlos I. 1 records from A new species of Dolichopoda (Orthoptera: Rhaphidophoridae; Dolichopodainae) from Western Greece. 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 7929 records from MEXU/Plantas Vasculares. 314 records from Tejidos colectados en la ventana de biodiversidad del Complejo Cenagoso de Zapatosa, Municipio de Chimichagua, Cesar, Colombia.. 1968 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 19 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 1540 records from Inventario de macroalgas de Bahía de Banderas: Fase I y Fase II. 74 records from New species of Sericini from Sri Lanka (Coleoptera, Scarabaeidae). 2 records from A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China. 310765 records from University of Michigan Museum of Zoology, Division of Insects. 1 records from Non Fish Species Occurrence in ASEAN Region. 3 records from A remarkable new species of the genus Lepisiota Santschi (Hymenoptera: Formicidae) from Oman and the United Arab Emirates with a key to the Arabian species. 54 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 15 records from Three new species of Entomobrya from Poland (Collembola, Entomobryidae). 20 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 50 records from Anfibios y reptiles de la expedición Monte y Pinal, Boyacá - Proyecto Boyacá BIO. 13 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 986 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 92 records from Review of the Australian Cyllodini (Coleoptera: Nitidulidae: Nitidulinae), with descriptions of new taxa, and notes on the genus Macleayania (Nitidulini). 10 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 2127 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 5 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 112818 records from New Zealand Arthropod Collection (NZAC). 5 records from Two new Colombian harvestmen of the genus Quindina Roewer, 1914 (Opiliones Nomoclastidae). 26 records from Epimeria of the Southern Ocean with notes on their relatives (Crustacea, Amphipoda, Eusiroidea). 15 records from Three new species of Miroculis from the Serra da Mocidade National Park, Roraima State, Brazil, with new records and checklist of the Leptophlebiidae (Ephemeroptera). 2 records from First description of the last instar larva and pupa of the aquatic crane fly Limnorimarga limonioides (Alexander, 1945) (Diptera: Limoniidae). 4 records from New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae). 2712 records from Collection Ichthyologie - SNSD. 2621 records from Fungi specimens of Saitama Museum of Natural History. 20520 records from University of Guam Insect Collection. 116 records from Taxonomic revision of the Colombian Tityus (Archaeotityus) (Scorpiones, Buthidae) species: a morphological and morphometric approach, with a description of a new species. 2 records from Dermaptera of Iran with description of Euborellia angustata sp. nov.. 6587 records from Actualización de la base de datos del Herbario de la Universidad de Sonora (USON). 3 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 1 records from Review of the Oriental genus Neoperlops Banks, 1939 (Plecoptera: Perlidae). 570 records from Zoocenosis of the mole burrows in the forest zone of Western Siberia. 6 records from Revision of the shore-fly genus Peltopsilopa Hendel (Diptera: Ephydridae). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 1 records from Taxonomy and Natural History of Strumigenys thaxteri Wheeler and Strumigenys reticeps (Kempf) (Hymenoptera: Formicidae). 1 records from First record of Orthelimaea himalayana (Ingrisch, 1990) (Orthoptera: Tettigoniidae: Phaneropterinae: Elimaeini) from India with description of its female. 2904 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche (Plantas). 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 24 records from Untangling the trees: Revision of the Calumma nasutum complex (Squamata: Chamaeleonidae). 1 records from A new Rhopalomeris species (Diplopoda: Glomerida: Glomeridae), and notes on the phylogenetic relationships between glomeridans in Vietnam. 26 records from Chaoborus flavicans Meigen (Diptera, Chaoboridae) is a complex of lake and pond dwelling species: a revision. 3 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 12 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 6 records from The crane fly genus Libnotes Westwood, 1876 (Diptera: Limoniidae) for Korea including two new species and an identification key. 1 records from A new subterranean Maraenobiotus (Crustacea: Copepoda) from Slovenia challenges the concept of polymorphic and widely distributed harpacticoids. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 2 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 34 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 4 records from Adventive Staphylinidae (Coleoptera) of the Maritime Provinces of Canada: further contributions. 7283 records from Colecção Entomológica IIA. 30 records from Equinodermos de las unidades ecológicas someras Expedición Seaflower Serranilla2017 - Proyecto Colombia BIO. 9 records from The first data on species diversity of leeches (Hirudinea) in the Irtysh River Basin, East Kazakhstan. 1070 records from Colección Ictiológica del Museo de Historia Natural de la Universidad de la Amazonia (UAM-P). 1 records from Eight species in the Nebela collaris complex: Nebela gimlii (Arcellinida, Hyalospheniidae), a new species described from a Swiss raised bog. 1 records from Record of a new species of the genus Viridopromontorius Luna de Carvalho (Strepsiptera: Corioxenidae) from India with a revised key to Corioxenidae. 322 records from Tetranychus urticae collection records in a predator-prey system: Phytoseiulus persimilis (Acari: Phytoseiidae) and Tetranychus urticae (Acari: Tetranychidae). 2434 records from Colección Mastozoológica del IADIZA - CCT CONICET Mendoza: IADIZA-CMI. 6 records from Rango, comportamiento, tamaño de población y conservación de felinos en el Volcán de Colima. 4127 records from University of Alberta Freshwater Invertebrate Collection (UAFIC). 1 records from A New Subspecies Of Chrysolina Sanguineocincta (Crotch, 1871) From Turkey (Coleoptera: Chrysomelidae: Chrysomelinae). 1068 records from DMNS Egg Collection (Arctos). 853 records from A taxonomic revision of the African genus Desplatsia Bocq. (Malvaceae - Grewioideae). 13203 records from Lepidopterous specimens of Yamagata Prefectural Museum. 10 records from A new genus and species of Haplobainosomatidae (Diplopoda: Chordeumatida) from the MSS of the Sierra de Guadarrama National Park, central Spain. 7402 records from Helgeland Museum, Lepidoptera. 200 records from Pareronia butterfly specimens at Museum Zoologi Bogor, Indonesia. 16440 records from Colección Zoológica de la Universidad del Tolima (CZUT)- Ictiología. 41 records from The cicadas (Hemiptera: Cicadidae) of Peru including the description of twenty-four new species, three new synonymies, and thirty-seven new records. 2742 records from Plant (KIWE-PL). 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 7 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 193 records from The diversity of the genus Aricidea (Polychaeta: Paraonidae) from the Sea of Marmara, with descriptions of two new species and two new records for the Mediterranean fauna. 1 records from Coelogynopora schockaerti n. sp. (Proseriata: Coelogynoporidae), a remnant of a platyhelminth coldwater fauna in the northwestern Mediterranean?. 987 records from Orthoptera - SMF. 1 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 1 records from Amage imajimai sp. nov., a new species of Ampharetidae (Annelida: Polychaeta) from Japanese waters. 14232 records from Colección de Poales del Museo Botánico CORD - IMBIV. 1 records from Chilopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 4 records from Revision of Tynacantha Dallas with description of two new species (Hemiptera: Heteroptera: Pentatomidae: Asopinae). 1702 records from BioGIS - Bryophytes - HUJ collections. 25 records from Notes on Mediterranean Theridiidae (Araneae) – II. 2 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 3596 records from University of Vermont, Pringle Herbarium, North American lichens. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 1 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 65 records from Collection Coleoptera SMF. 45970 records from Herbarium Universitatis Daugavpiliensis. 592 records from Colección de Entomología - Curculionidae. 763 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 6 records from Validation of Stenus (Hypostenus) primivenatus and Stenus (Hypostenus) yiae (Coleoptera, Staphylinidae, Steninae). 1 records from Description and bioecology of two new species of the genus Cryncus (Orthoptera Gryllidae, Gryllinae) from Cameroon with a key and distribution map of all African species. 13 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 1 records from A new acotylean flatworm, Armatoplana colombiana n. sp. (Platyhelminthes: Polycladida: Stylochoplanidae) from the Caribbean coast of Colombia, South America. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 1 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 44 records from Three new species and two new records of the genus Cotesia Cameron (Hymenoptera: Braconidae) from Iran. 16519 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 18 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Mollusca (ZUFMS-MOL). 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 2641 records from KTU Pteridophyta. 4357 records from Shellfish specimens of the Nishinomiya Shell Museum, Japan. 1 records from A new species of Hippopsis Lepeletier & Audinet-Serville, 1825 from Panama and key to species (Coleoptera, Cerambycidae, Lamiinae). 6230 records from Plecoptera. 5 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 9 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 2 records from First report of the spider genus Desis (Araneae, Desidae) from China, with description of a new species. 10 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 4 records from A new species Cyrtodactytlus Gray (Squamata: Gekkonidae) from western Thailand and the phylogenetic placement of C. inthanon and C. doisuthep. 184 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 2 records from Water striders (Heteroptera: Gerromorpha: Gerridae) of Romania with an update on the distribution of Gerris gibbifer and G. maculatus in southeastern Europe. 12 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 543 records from The Dr. Laurie L. Consaul Herbarium. 981 records from Bees in the UVM Zadock Thompson Zoological Collection. 14 records from NZCS Brownsberg Nature Park Monitoring. 47073 records from ANTARCTIC PLANT DATABASE. 1 records from Craspedorrhynchus linardii, a new species of chewing louse (Phthiraptera: Ischnocera: Philopteridae) from the Gray-headed Kite (Aves: Falconiformes: Accipitridae). 36297 records from Field Museum of Natural History (Botany) Fungi Collection. 5494 records from SJRP - Herbário de São José do Rio Preto. 6 records from Review of the moray eels (Anguilliformes: Muraenidae) of the Red Sea, with description of a new species. 2 records from A new species of Campylocia Needham & Murphy, 1924 (Ephemeroptera, Euthyplociidae) from Northern Brazil. 35 records from Ibaraki Nature Museum, Amphibians and Reptiles collection. 35 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 20 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 2 records from Description of a new species of Cosmocerca Diesing, 1861 (Nematoda Cosmocercidae) in Hoplobatrachus crassus (Jerdon, 1853) (Anura: Dicroglossidae from Asansol coal-field area, West Bengal, India. 39 records from Huangilene, a new genus for the Miltochrista alikangiae (Strand, 1917) species-group, with descriptions of three new species from Indochina, continental China and Taiwan (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 17 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 7 records from Pilargidae (Annelida: Phyllodocida) from coastal and deep waters of the Southwestern Atlantic, with descriptions of two new species. 724 records from Sistemática y biogeografía del género Xenosaurus (Squamata: xenosauridae). 59788 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 7058 records from Scarabaeoidea y colección de tipos de la colección entomológica del Centro de Estudios en Zoología, Universidad de Guadalajara. 192 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 22 records from New species of the orb-weaving spider genus Chrysometa (Araneae, Tetragnathidae) from oak forests near of the Pico de Orizaba National Park (Veracruz, Mexico). 147 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 5 records from Three new brackish-water thalassocypridine species (Crustacea: Ostracoda: Paracyprididae) from the Ryukyu Islands, southwestern Japan. 19 records from Unraveling the white-clothed Diestostemma Amyot & Serville: a taxonomic revision of the American sharpshooters of the D. bituberculatum complex (Hemiptera: Cicadellidae). 1 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 117 records from Estrutura e composição das comunidades de peixes em lagoas do Parque Nacional da Restinga de Jurubatiba. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 104152 records from The Himalayan Uplands Plant database (HUP Version 1). 42195 records from DMNH Birds. 1315 records from National Museum of Natural Science. 419 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 870 records from Database on reference specimens for medicinal plants of the Euphorbiaceae family, conserved at the CNARP herbarium. 1156 records from Collection tropical liverworts serving as vectors for symbiotic fungi at the Staatliches Museum für Naturkunde Stuttgart. 130 records from The millipede genus Leucogeorgia Verhoeff, 1930 in the Caucasus, with descriptions of eleven new species, erection of a new monotypic genus and notes on the tribe Leucogeorgiini (Diplopoda: Julida: Julidae). 26 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 42 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 52 records from Collections ichtyologiques et herpétologiques (BOUM). 1085 records from Rutgers University, Chrysler Herbarium - Lichen Collection. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 1 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 5 records from First record of the genus Tanaostigma (Hymenopteraı Chalcidoideaı Tanaostigmatidae) from the Afrotropical region with description of three new species. 2 records from New species of Silhouettea (Teleostei: Gobiidae) from Qeshm Island, Iran and the DNA barcoding of the Persian Gulf and Oman Sea gobies. 140 records from Collection Gilles Becquet (BOUM). 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 10 records from New species of Pseudoscorpiones (Arachnida) from tree hollows in a Mediterranean oak forest in Spain. 1211 records from CCBER Herpetology Collection. 2 records from A new four-pored Amphisbaena (Squamata: Amphisbaenidae) from northeastern Brazil. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 506 records from Base de datos sobre los hongos anamorfos de restos de vegetales del bosque mesófilo del estado de Veracruz. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 6 records from Modelaje de la distribución potencial de 10 especies de anfibios y reptiles en riesgo de extinción con escasos registros de presencia (PLECHA). 661 records from Catálogo de autoridades taxonómicas de Cyanoprocaryota marinos bentónicos de México. 1 records from Review of the genus Pogonolaelaps Nemati & Gwiazdowicz (Acari: Laelapidae) with description of a new species from Iran. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 2 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 1 records from A new distinctive species of Barydesmus (Diplopoda, Polydesmida, Platyrhacidae) from Ecuador, with an annotated bibliographical checklist of the American Platyrhacidae. 9883 records from University of Nebraska State Museum Birds Collection. 29735 records from University of California Santa Barbara Invertebrate Zoology Collection. 7 records from A review of the taxonomy and osteology of the Rhombophryne serratopalpebrosa species group (Anura: Microhylidae) from Madagascar, with comments on the value of volume rendering of micro-CT data to taxonomists. 2 records from Neue Milbenarten aus Kärnten. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 4 records from Two new species and new records of the Pselaphodes - complex of genera from China (Coleoptera: Staphylinidae: Pselaphinae). 29 records from Review of Palpostilpnus Aubert (Hymenoptera, Ichneumonidae, Phygadeuontinae), with the description of ten new species. 2 records from Vietnamella chebalingensis, a new species of the family Vietnamellidae (Ephemeroptera) from China based on morphological and molecular data. 6685 records from Herpetofauna del Estado de Veracruz. 72325 records from Entomology Collection at the Natural History Museum of Utah. 918 records from BHCB-Bryophyta - Herbário da Universidade Federal de Minas Gerais - Bryophyta. 5460 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 1 records from A new species of Cladotanytarsus (Lenziella) from Oregon supports the systematic concept of the subgenus (Diptera: Chironomidae). 3 records from Morphological and molecular characterization of Klossnema viguerasi n. sp (Nematoda: Oxyuridomorpha: Hystrignathidae) from a Cuban passalid beetle (Coleoptera: Passalidae), first record of the genus for Cuba. 863 records from Inventarios florísticos en Baja California Sur (II): Vegetación costera. 137 records from Hartland Nature Club Lepidoptera Collection. 209038 records from Australian National Insect Collection. 86047 records from ALCB - Herbário Alexandre Leal Costa. 9 records from Herbarium specimens of Limoges university (LIMO). 3750 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 2 records from A review of the genus Labeo (Teleostei: Cyprinidae) in Sri Lanka. 2 records from Papuaneon, a new genus of jumping spiders from Papua New Guinea (Araneae: Salticidae: Neonini). 916 records from Distribution of aquatic beetles from the east of Morocco (Coleoptera, Polyphaga). 142 records from Colección Ictiológica del Museo de Historial Natural, Universidad de Caldas. 1 records from Redescription of four species of Cytaea Keyserling, 1882 (Araneae: Salticidae). 1189 records from UWIZM Molluscs. 3 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 11 records from Paracobitis abrishamchiani, a new crested loach from the southern Caspian Sea basin (Teleostei: Nemacheilidae). 2 records from New species of Simothraulopsis Demoulin, 1966 (Ephemeroptera: Leptophlebiidae) from Northeastern Region of Brazil. 1 records from A revision of the genus Bryolymnia Hampson in North America with descriptions of three new species (Lepidoptera, Noctuidae, Noctuinae, Elaphriini). 2 records from Description of a new diminutive Hyloxalus (Anura: Dendrobatidae: Hyloxalinae) from the Magdalena Valley of Colombia. 38500 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Herpetology National Collection (MACNHe). 4083 records from MCP-Aves - Coleção de Aves. 5880 records from Plantas de La Frontera (ecorregión 12.1.1.1), e inventario florístico del Rancho El Aribabi, municipio de Imuris, Sonora. 138 records from New species of gall fly (Diptera: Fergusoninidae) from Eucalyptus camaldulensis (Myrtaceae) in southern Australia and its associated parasitoids and inquilines. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 10777 records from Fungi collection of Jyväskylä University Museum. 1187 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase II (Tlahuelompa y Eloxochitlán). 14 records from Nemertini - SMF. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 778 records from Bird specimens of Saitama Museum of Natural History. 371 records from orthopteracollections-nhmj-ioj. 1 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 9490 records from Aves Tanzanian collection at the Natural History Museum of Denmark (SNM). 36 records from Occurrence of some antityphod plants from Cameroon. 611 records from Troides butterfly specimens at Museum Zoologi Bogor, Indonesia. 2 records from A new canopy-dwelling species of Dendrelaphis (Serpentes: Colubridae) from Sinharaja, World Heritage Site, Sri Lanka. 56 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 6 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 625 records from Mycology collection, Norwegian Forest and Landscape Institute. 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 47434 records from DMNS Bird Collection (Arctos). 2 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 6068 records from Plant specimens of Tama City Cultural Foundation. 1 records from A new species and key to all known species of the genus Filchnerella Karny, 1908 from China (Orthoptera: Acridoidea, Pamphagidae). 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 1 records from Neoclita pringlei (Scarabaeidae, Cetoniinae), a new relict genus and species from the Drakensberg Range of South Africa. 38278 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 34 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 277417 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 93 records from Poliquetos (Annelida: Polychaeta) del Pacífico Mexicano. 1 records from A new species of Acrotaphus Townes (Hymenoptera: Ichneumonidae: Pimplinae) from the Brazilian Amazon, with notes on its host spider behavioral modification. 1 records from Stylogomphus thongphaphumensis (Odonata: Anisoptera: Gomphidae), a new gomphid dragonfly and the first record of S. malayanus Sasamoto, 2001 from Thailand. 1904 records from Escarabajos coprófagos de la cuenca alta y media del río Bita, Vichada (Colombia). 173 records from UWIZM Anoles. 140 records from Revision of the morphology, phylogenetic relationships, behaviour and diversity of the Iberian and Italian ant-like Tachydromia Meigen, 1803 (Diptera: Hybotidae). 7 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 3 records from Dolichocaudus, a new genus in the leafhopper subfamily Evacanthinae (Hemiptera: Cicadellidae), with description of two new species. 2 records from Four new species of Goloboffia (Mygalomorphae: Migidae) from Chile. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 1 records from A new species of Lithophane Hbn. (Lepidoptera, Noctuidae, Xyleninae). 2451 records from Macrobenthos Chukchi Sea, 1986. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 9 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 367 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 4 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 15 records from Tardigrad collection of the National Museum of Nature and Science. 3 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 8 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 88 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 16071 records from Herbier Louis-Marie (QFA) - Collection de lichens. 1363 records from Actualización de la Colección de Microorganismos de importancia acuática. 2 records from Morphology and molecules say: Tanytarsus latens, sp. nov. from Finland (Diptera: Chironomidae). 3 records from A new genus and species of natricine snake from northeast India. 11 records from Revisions of two poorly known species of Opisthotropis Günther, 1872 (Squamata: Colubridae: Natricinae) with description of a new species from China. 4093 records from Brown University. 3923 records from Grasses of the Forest Herbarium Ibadan (FHI) Nigeria. 80315 records from Fish specimens of Kagoshima University Museum. 3825 records from UTEP Invertebrates (Arctos). 40 records from Rivaling the World’s Smallest Reptiles: Discovery of Miniaturized and Microendemic New Species of Leaf Chameleons (Brookesia) from Northern Madagascar. 112 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 3 records from Taxonomic revision of the species of Colletes Latreille, 1802 (Hymenoptera: Colletidae: Colletinae) found in Chile. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 10 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 10 records from Seven new species of Australian peacock spiders (Araneae: Salticidae: Euophryini: Maratus Karsch, 1878). 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 5909 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 45433 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 5 records from A new deep-water species of Alpheopsis Coutière, 1897 from the Indo-West Pacific (Decapoda: Alpheidae). 12 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 325 records from Diversidad genética del cultivo del chile (Capsicum spp) determinada por isoenzimas y RFLP's tipos: serrano, jalapeño, manzano y silvestres en su área de distribución. 7 records from Revision of Chaetacanthus Seidler, 1922 (Annelida, Phyllodocida, Polynoidae). 1308 records from Slovenian Fungal Database - Boletus informaticus. 1367 records from Flora útil del Municipio de la Huerta, Jalisco. 1910 records from Chucki_Seaooplankton1953/4. 2 records from Review of the New World genus Nanium Townes, 1967 (Hymenoptera: Ichneumonidae: Ctenopelmatinae), with two new species from the Neotropical region. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 1149 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 206 records from The Diptera Site. 20 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 3 records from Mangelia (Gastropoda, Conoidea) species of the Turkish coasts with description of Mangelia vanaartseni sp. nov.. 122 records from Base de datos de las especies maderables del género Dalbergia en México, registros del Herbario Nacional de México (MEXU). 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 4 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 47 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 14 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 9 records from Contribution to the knowledge of the dentipes group of the genus Brachiacantha (Coleoptera: Coccinellidae). 48 records from Identity of bryozoan species described by Jullien & Calvet from the Bay of Biscay historically attributed to Smittia. 267172 records from hymenoptera. 1615 records from Naturalis Biodiversity Center (NL) - Crustacea. 17 records from The West Palaearctic Dineura species, focussing on Sweden (Hymenoptera, Tenthredinidae). 21 records from Brown algae specimens of Komatsu City Museum. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 3 records from A new species of Protonemura Kempny, 1898 (Plecoptera: Nemouridae) from the Ishizuchi range, Shikoku, Japan. 3 records from Contribution to the genus Anomala Samouelle, 1819 (Coleoptera: Scarabaeidae Rutelinae) of China and adjacent regions. Part I: descriptions of two new species and remarks on four species. 1 records from Description of a new genus and species of the subfamily Arcoscalpellinae Zevina, 1978 (Cirripedia: Thoracica: Scalpellidae) from deep waters of the South China Sea. 273 records from BMHS Herbarium Collection. 1166 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 536 records from Ascomycetes of Russian Fennoscandia. 25 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 11 records from MO herbarium - Missouri Botanical Garden - Amostras Brasileiras Repatriadas - Herbário Virtual REFLORA. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 1477 records from The Broward College Insect Collection. 370 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 3583 records from Colecção Entomológica do Departamento de Sanidade Vegetal - Ministério da Agricultura e Segurança Alimentar. 573 records from Ibaraki Nature Museum, Mammals collection. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 14 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 4 records from Pterophoridae (Lepidoptera) fauna of the Republic of Tuva. 41 records from NEON Biorepository Zooplankton Collection (DNA Extracts). 11 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 3 records from Rediscovery and redescription of a deep-sea shrimp Lebbeus longidactylus (Kobjakova, 1936) (Crustacea: Decapoda: Caridea: Thoridae) based on material from the Nemuro Strait, southwestern Sea of Okhotsk. 3 records from Oxynoemacheilus shehabi, a new nemacheilid loach from the upper Orontes in southern Syria (Teleostei: Nemacheilidae). 87 records from Guasuctenus gen. nov., a new Neotropical spider genus of Ctenidae (Araneae). 53221 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 2 records from Transfer of two South American ant species from Tapinoma Foerster 1850 to Forelius Emery 1888 (Hymenoptera: Formicidae: Dolichoderinae). 3 records from Description of two new species of Seinura Fuchs, 1931 (Nematoda: Aphelenchoididae) from Iran. 1 records from Description of the adult and larva of Clunio balticus Heimbach, 1978 (Diptera Chironomidae) from the seashore of Bergen (Norway). 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 4 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 22 records from Description of Bagarius vegrandis, a new species of sisorid catfish from Indochina (Actinopterygii: Siluriformes), with notes on the identity of Bagarius bagarius. 2226 records from Weber State University Herbarium. 4 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 11 records from An annotated checklist of the Iranian Brentidae (Coleoptera: Curculionoidea). 6 records from Historic Lady Beetle Records (Coccinellidae) from Mt. Mansfield, Vermont , USA: 1991-1994. 2 records from New record of the steppe longhorn beetle species Phytoecia (Musaria) argus (G. F. Frölich, 1793) (Cerambycidae: Lamiinae) in Bulgaria. 2 records from An interesting new species of Kamimuria (Plecoptera: Perlidae) from China, with notes on K. grandispinata Du & Sun. 553 records from Molecular phylogeny of the genus Lasiopogon (Diptera: Asilidae) and a taxonomic revision of the bivittatus section. 6 records from Correctly mating: on the actual female of Hibana talmina Brescovit and the description of H. labonita sp. n. (Araneae, Anyphaenidae). 7732 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 29 records from Genera of the Asian Catfish Families Sisoridae and Erethistidae (Teleostei: Siluriformes).. 60 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 6 records from Transfer of the Namibian Argistes africanus Simon, 1910 (Araneae: Liocranidae) to Afroceto Lyle & Haddad, 2010 (Trachelidae), with a new synonym. 29 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 4 records from Two new species of the armored spider genus Tetrablemma O. P. - Cambridge, 1873 from northern South America (Araneae: Synspermiata: Tetrablemmidae). 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 10 records from A new species of the spider genus Wirada (Araneae, Theridiidae) from Mexico, with taxonomic notes on the genus and a key to the species. 27749 records from SP-Bryophyta - Maria Eneyda P. Kauffman Fidalgo. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 3 records from Rediscovery of a fossil dolichoderine ant lineage (Hymenoptera: Formicidae: Dolichoderinae) and a description of a new genus from South America.. 1 records from Trachyuropodid mites (Acari: Uropodina) from South-East Asia: catalog, new key and description of two new species. 10 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 1 records from A new aquatic beetle family, Meruidae, from Venezuela (Coleoptera: Adephaga). 203 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 17 records from Plant-parasitic nematodes of Republic of Karelia. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 2 records from Neue Oribatiden (Acari) aus Deutschland III. Suctobelba carcharodon n. sp. und Suctobelba prominens n. sp.. 1 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 13 records from Yuelushannus gen. nov. (Araneae, Linyphiidae) from China. 14 records from On three new oonopid species from China and the discovery of the male Orchestina bialata Liu, Xiao & Xu, 2016 (Araneae: Oonopidae). 5 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 101 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 38 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 26106 records from Mycology herbarium, Tromsø Museum. 16 records from Insect Collections of Okomu National Park- Nigeria. 208102 records from University of Minnesota Insect Collection. 3 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas I. Zwei neue Arten der Gattung Suctobelba Paoli aus der Oberlausitz (DDR): Suctobelba scalpellata n. sp. und Suctobelba secta n. sp.. 5 records from A review of the stink bug genus Plautia Stål from Japan (Hemiptera, Heteroptera, Pentatomidae). 135311 records from ARABEL - Arachnologia Belgica. 8 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 8 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 1 records from Cryptotermes camelus (Isoptera: Kalotermitidae), a new drywood termite species from the Bolivian Chaco. 174 records from Antarctic pycnogonids. 1 records from Laubuka parafasciata, a new cyprinid fish species (Teleostei: Cyprinidae) from Mizoram northeastern India. 60949 records from MLZ Bird Collection (Arctos). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 1 records from Description of Malenchus gilanensis n. sp. from Iran. 5 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 14 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 1 records from Two new species of freshwater, cave-dwelling crabs of the genus Neostrengeria Pretzmann, 1965, from Colombia (Crustacea: Decapoda: Pseudothelphusidae). 5 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 4 records from A new small-sized Theloderma (Anura: Rhacophoridae) from Laos. 2 records from Notes on species of the genus Chlaenius Bonelli, 1810 (Coleoptera: Carabidae, Chlaeniini) from four agro-climatic zones of Rajasthan, with description of two new species. 3 records from Taxonomic revision of the Mexican Eucyclops (Copepoda: Cyclopoida) with comments on the biogeography of the genus. 18 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 1 records from Sarcocheilichthys vittatus, a new species of gudgeon (Teleostei: Cyprinidae) from the Poyang Lake Basin in Jiangxi Province, South China. 2 records from Validity of Psammoperca datnioides Richardson 1848 and redescriptions of P. waigiensis Cuvier in Cuvier & Valenciennes 1828 and Hypopterus macropterus (Günther 1859) in the family Latidae (Perciformes) from the Indo-West Pacific. 9042 records from Northern Biodiversity Program Coleoptera (2010-2011). 1 records from New records of Synallactes virgulasolida Massin & Hendrickx, 2010 (Echinodermata: Holothuroidea) from the eastern Pacific. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 11 records from Systematic notes on some leptomedusa species with a description of Neotima galeai n. spec. (Hydrozoa, Cnidaria). 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 197 records from Some Museums-Meloidae-Biodiversity-Records. 5 records from Neotropical osmylids (Neuroptera, Osmylidae): Three new species of Isostenosmylus Krüger, 1913, new distributional records, redescriptions, checklist and key for the Neotropical species. 5 records from Description of the lucky Cophyla (Microhylidae, Cophylinae), a new arboreal frog from Marojejy National Park in north-eastern Madagascar. 10 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleopalynology National Collection (BAPal). 232 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 1 records from Nemertean specimens of Ryukyu University Museum (Fujukan). 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 25 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 115 records from Living Cirripedia. 2208 records from Inventario florístico de Tetipac y sus alrededores (Sierra de Taxco). 7 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 148 records from Flora de los ecosistemas de la zona alta del río Coello (Tolima, Colombia). 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 1 records from Tazarcus, a new phylogenetically unplaced genus of two flightless weevils with metapleural ridge from the Eastern Arc Mountains, Tanzania (Coleoptera: Curculionidae: Molytinae). 637 records from MNA (Section of Genoa) - Marine Biological Samples. 7 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). I. Gracilipalpe, morchella and nigrum groups. 381 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 207 records from NEON Biorepository Zooplankton Collection (Remaining Bulk Taxonomy Sample). 4 records from A remarkable new species of Micropeza Meigen (Diptera: Micropezidae) from Caatinga biome, Brazil. 31 records from Geographic structure of genetic variation in the Parachute Gecko Ptychozoon lionotum Annandale, 1905 across Indochina and Sundaland with descriptions of three new species. 5 records from Two new endemic species of Bistriopelma (Araneae: Theraphosidae) from Peru, including a new remarkable horned tarantula. 2126 records from NU: KwaZulu-Natal Invasive Alien Species (1821-2011). 64915 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 1994 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 5 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 18 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 9 records from New host and distribution records for Buprestidae (Coleoptera) from the state of Morelos, Mexico. 7 records from First record of the genus Agnara (Isopoda: Oniscidea) from Iran with descriptions of two new species. 25 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 16582 records from MAC herbarium - Instituto do Meio Ambiente do Estado de Alagoas - Herbário Virtual REFLORA. 1 records from Soil-inhabiting mites of the family Laelapidae (Acari: Mesostigmata) from Assiut Governorate, Egypt. 1 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 49 records from Museu Paraense Emílio Goeldi - Myriapoda Collection. 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 36832 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 8 records from The Trichoptera of Panama. XII. Contributions to the family Glossosomatidae (Insecta: Trichoptera) in Panama. 3 records from Taxonomic revision of the Palaearctic Tetramorium chefketi species complex (Hymenoptera: Formicidae).. 2 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 2 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 50 records from Empria and Monsoma in Japan. 321 records from Vegetación de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 1 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 18 records from Kinorhyncha specimens of Ryukyu University Museum (Fujukan). 1 records from Reptilia ZMK. 6 records from Unexpected discovery of six new species of Aphyosemion (Cyprinodontiformes, Aplocheilidae) in the Wonga-Wongué Presidential Reserve in Gabon. 71718 records from Ibaraki Nature Museum, Vascular Plants collection. 5 records from Redescription of the poorly known crab spider Xysticus spasskyi (Araneae: Thomisidae). 1290 records from Diversity of Spiders from Azorean Trails. 262 records from Plants Of Nnamdi Azikiwe University Herbarium (NAUH) Awka. 4976 records from Sistematización de la colección entomológica y actualización de la colección del herbario CHIP del Instituto de Historia Natural y Ecología (IHNE), Chiapas (Insectos). 1 records from A redescription of Moina australiensis Sars, 1896 (Cladocera: Moinidae) with short notes on Australian moinids. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 911 records from Museo de Historia Natural Universidad de Caldas - Colección de Vertebrados e Invertebrados - Anfibios. 5870 records from Digitization of plant specimens from Rhoen and Vogelsberg (FULD). 18 records from Three new generic records and descriptions of four new species of jumping spiders (Araneae, Salticidae) from Sri Lanka. 498230 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 1 records from On a new species of Euchondrus Boettger, 1883 from Syria (Pulmonata: Enidae). 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 71 records from Revision of Brada Stimpson, 1853, and Bradabyssa Hartman, 1967 (Annelida, Flabelligeridae). 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 1 records from A new deepwater species of Calliopiidae, Halirages helgae (Crustacea, Amphipoda), with a synoptic table to Halirages species from the northeast Atlantic. 10283 records from Inventario de Hymenóptera; parasítica en México. 3 records from Onuphi s and Mooreonuphis (Annelida: Onuphidae) from West Africa with the description of three new species and the reinstatement of O. landanaensis Augener, 1918. 8561 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 3 records from Dichromatobolus, a new genus of spirobolidan millipedes from Madagascar (Spirobolida, Pachybolidae). 2 records from Sinopyrophorinae, a new subfamily of Elateridae (Coleoptera, Elateroidea) with the first record of a luminous click beetle in Asia and evidence for multiple origins of bioluminescence in Elateridae. 15057 records from Insect Collection of Saitama Museum of Natural History. 715 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 9 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 3 records from Two new species of lotic breeding salamanders (Amphibia, Caudata, Hynobiidae) from western Japan. 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 1 records from A new edible cricket species from Africa of the genus Scapsipedus. 1573 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 47 records from Re-classification of Lycoriella Frey sensu lato (Diptera, Sciaridae), with description of Trichocoelina gen. n. and twenty new species. 82 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 1 records from A revision of the genus Hypotrix Guenee in North America with descriptions of four new species and a new genus (Lepidoptera, Noctuidae, Noctuinae, Eriopygini). 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 414 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 678 records from Lucanidae. 2 records from SyNoeca ilheeNsis sp. nov., a new social wasp (Hymenoptera, Vespidae, Polistinae) from Brazilian lowland Atlantic Forest. 29 records from New species, synonymy and records of Endomia and Stenidius (Coleoptera: Anthicidae) from Asia. 54 records from IBF Monitoring of Plant Galls. 27670 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 276 records from Birds Specimens of Akita Prefectural Museum. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 1139 records from Herpetofauna de la región El Huizache, San Luis Potosí. 41 records from MSUM Ichthyology and Herpetology Collections. 1 records from Notes on west Palaearctic species of the genus Trigonurus Mulsant, 1847 (Coleoptera: Staphylinidae: Trigonurinae). 1 records from Bryozoans Specimens of Akita Prefectural Museum. 9 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 2 records from Two new species of the genus Malayepipona Giordani Soika (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with updated key to all recognised species. 1 records from A new species of Aphelocheirus (Hemiptera: Heteroptera: Aphelocheiridae) from Morocco. 1901 records from Inventario avifaunístico de las áreas focales Zoh-Laguna y La Montaña en el corredor biológico mesoamericano Sian Ka'an- Calakmul, México. 52 records from Distribución, abundancia y selección de hábitat de especies de aves amenazadas y en peligro de extinción en los bosques de montaña de Chiapas. 17 records from Database on reference specimens for medicinal plants of the Araceae family, conserved at the CNARP herbarium. 1 records from Thraulodes marianoi sp. nov., a remarkable new species of mayfly (Ephemeroptera Leptophlebiidae) with dark wings from the southern Brazilian Atlantic Forest. 1 records from Redescription of three species of Apobaetis Day, 1955 (Ephemeroptera: Baetidae). 2 records from The dark side of pumpkin toadlet: a new species of Brachycephalus (Anura: Brachycephalidae) from Serra do Brigadeiro, southeastern Brazil. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 1 records from Tibetyrus gen. nov., a new myrmecophilous Tyrini from Xizang, China (Coleoptera: Staphylinidae: Pselaphinae). 5 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 286 records from California State University, Long Beach Birds. 9061 records from CNMT - Herbário Centro Norte Mato Grossense. 1 records from A New Record From The Genus Callicera Panzer, 1809 (Insecta: Diptera: Syrphidae) From India. 351 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 4 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 141 records from Collection Hydrozoa - ZSM München. 927 records from RMT Trawl catch from the 1982/83 V2 ADBEX I voyage. 3 records from The eel genus Macrocephenchelys (Anguilliformes: Congridae) in Taiwan, with description of a new species. 3580 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 17472 records from Royal Museum of Central Africa - True Fruit Flies (Diptera, Tephritidae) of the Afrotropical Region (ENBI wp13). 187088 records from Geneva Herbarium – General Collection (G). 21 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 271 records from Vegetación de los remanentes de bosque andino, municipio de San Francisco (Cundinamarca). 62 records from Characidium longum (Characiformes: Crenuchidae), a new fish from Venezuela.. 4778 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 367 records from QLD DERM Coastal Bird Atlas (Trial). 14295 records from SPSF - Herbário Dom Bento José Pickel. 131 records from Some thecate hydroids (Cnidaria: Hydrozoa) from off New Caledonia collected during KANACONO and KANADEEP expeditions of the French Tropical Deep-Sea Benthos Program. 1 records from Taito adrik, a new harvestman species from the Área de Conservación Privada Panguana, Peruvian Amazonia (Opiliones: Laniatores: Cosmetidae). 13 records from Adding stars to the Chromodoris (Nudibranchia, Chromodorididae) galaxy with the description of four new species. 5 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 1158 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 73 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 1 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 11 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanteriidae).. 4974 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 2 records from Nothogreniera new genus, for two species of Australian " Paracnephia " (Diptera: Simuliidae). 1955 records from SIM-Fungal records compiled by Joan Montón. 747015 records from Western Australian Museum provider for OZCAM. 12547 records from El banco de datos del Herbario HCIB en línea (Fase I): Implementación del Sistema Biótica. 3992 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 419 records from Colección de mamíferos voladores y no voladores de la Universidad de Nariño. 9572 records from Colección de Hongos del Herbario de la Universidad de La Laguna: TFC Mic. 1 records from Description of a new species of the Melanorivulus pictus species-group (Cyprinodontiformes: Rivulidae) from the Rio Paraná basin in Brazil. 3 records from First records of Edwardsiana sociabilis (Ossiannilsson, 1936) and Laburrus pellax (Horváth, 1903) (Hemiptera, Auchenorrhyncha: Cicadellidae) in Switzerland. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 8 records from New species and records of Paraphloeostiba Steel, 1960 from China and Laos and descriptions of four new species of related genera (Coleoptera: Staphylinidae Omaliinae: Omaliini). 3 records from Bodotria paraspinifera sp. nov. (Crustacea: Cumacea: Bodotriidae), a new Korean cumacean. 839 records from CEPEC herbarium - Centro de Pesquisas do Cacau - Herbário Virtual REFLORA. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 33361 records from University of Hawaii Insect Museum. 2 records from Two new species of Austrotinodes Schmid (Insecta, Trichoptera, Ecnomidae) from southeastern Brazil. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 37 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 5205 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 140 records from Naturalis Biodiversity Center (NL) - Diptera. 2 records from A new species of Paralithoxus (Siluriformes: Loricariidae: Ancistrini) from the highlands of Serra da Mocidade, Roraima State, Brazilian Amazon. 26 records from A new species of Tricorythodes Ulmer (Ephemeroptera: Leptohyphidae) from Uruguay. 7 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 632 records from 2019_NSMK_PL. 2 records from Rediscovery of Glenurus incalis Banks (Neuroptera: Myrmeleontidae), and notes on the Brazilian species of Glenurus Hagen. 48 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1212 records from Records of Halicarcinus planatus at sub-Antarctic regions. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 1696 records from Herbier National de Guinée (HNG). 1 records from Phylogenetic position of two Macrobiotus species with a revisional note on Macrobiotus sottilei Pilato, Kiosya, Lisi & Sabella, 2012 (Tardigrada: Eutardigrada Macrobiotidae). 1 records from Out of the Neotropics: newly discovered relictual species sheds light on the biogeographical history of spider ants (Leptomyrmex, Dolichoderinae, Formicidae). 25 records from New records of Stenopygium Becker (Diptera: Dolichopodidae) from the Neotropical Region, and a key to species. 4479 records from Iowa State University Fishes Collection. 8 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 300 records from EDIT - ATBI in Gemer area (Slovakia). 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 1128888 records from Natural History Museum (London) Collection Specimens. 69 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 6 records from Notes on the genus Perittopus Fieber, 1860 (Hemiptera: Heteroptera: Veliidae with descriptions of three new species from Indochina. 5 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 11321 records from WOLL AVH data. 4602 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 3 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 1 records from A new genus and new species assigned to Macrophthalmidae (Decapoda: Brachyura: Thoracotremata) from the Ryukyu Islands, Japan. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 34 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 5 records from Six new and one known species of Geomonhystera (Nematoda, Monhysteridae) from moss, an epiphytic plant and soil in México and Ecuador. 572 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 20004 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 35 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 76115 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 94 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 865 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 1433 records from Collection botanique Jaubert et Saul (BOUM). 31 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 5 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 82 records from Modelación de la distribución real y potencial de especies de dos géneros de Mimosoideae: Mimosa y Prosopis (Leguminosae) en México (Mimosa). 2344 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 2 records from Two new species of Willowsia (Collembola: Entomobryidae) from Guizhou Province, China. 76 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 70 records from NZCS Sipaliwini Savanna Expeditions 1997/2014. 2 records from Two remarkable new species of oribatid mites (Acari: Oribatida) from Acacia litter of Kerala, India. 3 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 11 records from Phylogenomic re-evaluation of Triaenonychoidea (Opiliones: Laniatores), and systematics of Triaenonychidae, including new families, genera and species. 174 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 2380 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 8 records from The catshark genus Scyliorhinus (Chondrichthyes: Carcharhiniformes: Scyliorhinidae): taxonomy, morphology and distribution. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 8214 records from The Fungal Collection at the Botanische Staatssammlung München. 1 records from Calvariopsis gen. nov., a new genus of Neotropical Scirtidae (Coleoptera: Scirtoidea). 954 records from NW Pacific Deep-sea Benthos Biodiversity (Beneficial Project). 647 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 47432 records from Phanerogamic Botanical Collections (S). 7341 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 16 records from A study on the genus Stenus Latreille from Zhuji City of Zhejiang, East China (Coleoptera, Staphylinidae). 8 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 61 records from Herbarium specimens of Hokkaido University Museum. 2 records from Anisops sardeus Herrich-Schaeffer, 1849: first records from Hungary (Heteroptera: Notonectidae). 568 records from Philippine Mollusk Symbiont - ICBG Collection. 1 records from A New Genus and Species of Blind Sleeper (Teleostei: Eleotridae) from Oaxaca, Mexico: First Obligate Cave Gobiiform in the Western Hemisphere. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 486 records from Anfibios y reptiles del municipio de Cuetzalan del Progreso, Puebla. 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A new species of Xestophrys Redtenbacher, 1891 (Orthoptera: Tettigoniidae; Conocephalinae; Copiphorini) from India. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 1931 records from Clémence Lortet herbarium. 1 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 37 records from Revision of the genus Platyscelis Latreille, 1818 from China (Coleoptera: Tenebrionidae: Platyscelidini). 14 records from Australian Marsh Beetles (Coleoptera: Scirtidae). 9. The relations of Australasian Ypsiloncyphon species to their Asian congeners, additions, mainly to Petrocyphon and Prionocyphon, and a key to Australian genera of Scirtinae. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 3 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 5 records from Modelaje de la distribución potencial de 10 especies de anfibios y reptiles en riesgo de extinción con escasos registros de presencia (CHIMUL). 1 records from Acantorna-a new genus of Hymedesmiidae (Porifera, Demospongiae Poecilosclerida) from the western Aleutian Islands of Alaska with description of Acantorna tahoma n. sp.. 2 records from A new species of rheophilic cyprinid fish (Teleostei: Cyprinidae) from the Brahmaputra Basin, northeast India. 2 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 16 records from Many things come in small packages: Revision of the clawless geckos (Crenadactylus: Diplodactylidae) of Australia. 8114 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 10 records from Meadow katydids (Orthoptera: Tettigoniidae: Conocephalini) from the Central-West Region of Brazil: Morphological, bioacoustic and cytogenetic study. 3 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 1 records from Additions to the taxonomy of the Afrotropical Tetramorium weitzeckeri species complex (Hymenoptera, Formicidae, Myrmicinae), with the description of a new species from Kenya. 7839 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 13 records from A revision of the spider genus Raveniola (Araneae, Nemesiidae). I. Species from Western Asia. 18 records from ZUEC-EPH - Coleção de Ephemeroptera do Museu de Zoologia da UNICAMP. 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 4 records from Mystus prabini, a new species of catfish (Siluriformes: Bagridae) from Arunachal Pradesh, north-eastern, India. 1 records from A new genus and species of congrid eel from the Philippines (Anguillliformes: Congridae: Bathymyrinae). 229 records from Colección Mastozoológica-Museo de Historia Natural Unillanos. 13 records from Coleção de Coleoptera da Universidade de Brasília. 44467 records from CSIC-Real Jardín Botánico-Colección de Hongos (MA-Fungi). 5044 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 80 records from New synonyms, combinations and status in the Chinese species of the family Meloidae Gyllenhal, 1810 (Coleoptera: Tenebrionoidea) with additional faunistic records. 2 records from The first record of the family Chloroperlidae (Plecoptera) from the Guangxi Zhuang Autonomous Region of southern China, with description of a new species of Sweltsa Ricker, 1943. 6 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 7071 records from Marie-Victorin Herbarium (MT) - Bryophytes. 26 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 2 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 2 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 2103 records from 2019_biodiversity_cooperation_investigation. 59 records from Neostasina gen. nov., a new genus of huntsman spiders from the Neotropical region (Araneae, Sparassidae, Sparianthinae). 17 records from A new species and new country records for the genus Leptobium Casey in the Palaearctic Region (Coleoptera: Staphylinidae: Paederinae). 1 records from Isoperla vjosae sp. n., a new species of the Isoperla tripartita group from Albania (Plecoptera: Perlodidae). 3 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 1 records from Three New Species of Dendrogaster (Crustacea: Ascothoracida) Infecting Goniasterid Sea-Stars (Echinodermata: Asteroidea) from Japan. 2 records from thysanorea. 162 records from New data on spiders (Aranei) from the Maritime Province, Russian Far East. 3239 records from Arthropods from Praia da Vitória (Terceira, Azores, Portugal). 1668 records from Utah State University, Intermountain Herbarium. 2 records from Trachelus stipa (Hymenoptera: Cephidae), a new stem sawfly from Central Anatolia associated with feather grass (Stipa holosericea, Poaceae). 37946 records from K herbarium - Royal Botanic Gardens, Kew - Amostras Brasileiras Repatriadas - Herbário Virtual REFLORA. 19 records from Revision of the Barsine cardinalis - anomala ' species-complex' (Lepidoptera, Erebidae, Arctiinae). 26 records from A checklist of the Iranian Mordellidae (Coleoptera: Tenebrionoidea). 753 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 85154 records from CAS Entomology (ENT). 18 records from Swedish Malaise Trap Project (SMTP) - Diacritinae. 6086 records from Naturalis Biodiversity Center (NL) - Pisces. 54 records from Molluscan fauna of Gueishan Island of Taiwan. 27 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 28 records from Tenuiphantes zelatus (Zorsch), T. zibus (Zorsch), and Centromerus mariannae sp. nov. (Araneae: Linyphiidae) in the Pacific Northwest. 320 records from Marine algal (seaweed) flora of Formigas Islets, Azores. 3 records from Two new records of palm species for Gabon: Sclerosperma profizianum Valk. & Sunder. and Eremospatha quiquecostulata Becc.. 4 records from The fossil avifauna of the tar seeps Las Breas de San Felipe, Matanzas, Cuba. 4 records from Two new species of Psephenops Grouvelle (Coleoptera: Byrrhoidea: Psephenidae) from Panama. 1 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 7600 records from ERBG AVH data. 4 records from Seven species of Pseudopecoeloides Yamaguti, 1940 (Digenea, Opecoelidae) from temperate marine fishes of Australia, including five new species. 61174 records from Tiroler Landesmuseum Ferdinandeum. 75 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 87 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 5 records from Evaluación de la situación de Tillandsia mauryana en el Apéndice II de la CITES, según su estado de conservación y comercio. 2 records from The first record of the genus Desertoniscus Verhoeff, 1930 (Isopoda, Oniscidea, Agnaridae) from Europe, with the description of a new species. 42 records from Twenty new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental Region. 2 records from Description of the female and egg of Phantasca phantasma (Westwood, 1859) (Phasmatodea: Diapheromeridae: Diapheromerinae). 2165 records from Prime Hoverfly (Insecta: Diptera: Syrphidae) Areas (PHA) as a conservation tool in Serbia. 2968 records from John Clayton's Fijian Moth Collection. 12 records from Species delimitation in the Gehyra nana (Squamata: Gekkonidae) complex: cryptic and divergent morphological evolution in the Australian Monsoonal Tropics, with the description of four new species. 2962 records from Data mobilized by the National Herbarium of Benin in the framework of the JRS Biodiversity project of Benin. 3 records from The genus Phlesirtes Bolivar, 1922 (Orthoptera: Tettigoniidae: Conocephalinae, Conocephalini; Karniellina), a review of the genus with data on its bioacoustics and the description of new species. 5 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 320 records from Myxomycetes collection of the University of Eastern Finland. 20 records from New data on the fauna of China, part I: the taxonomy of the millipede family Julidae (Diplopoda). 53 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 9 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 2389 records from PAMP-tracheo: Vascular plants in Pamplona Basin (Navarra, Spain). Undergraduate thesis, D. Vicente. 137 records from Insect Ichneumon fly (KIDR-IN). 6 records from A taxonomic revision of the genus Sirthenea (Hemiptera: Heteroptera: Reduviidae) of the Old World. 338 records from Fishes in MZNA-VERT: cyprinid and salmonid communities in the rivers Erro and Urederra (Spain). PhD project, Cristina García-Fresca. 127 records from Insect specimens of Tochigi Prefectural Museum. 2963 records from Collection Trichoptera - SMF. 16 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 3217 records from Lichenized fungi of Vietnam (PHH Herbarium, Cryptogam collection). 4170 records from VIT - Lepidotheca (The Natural History Museum of Álava). 107 records from Bases de datos de Tanaidaceos (Crustacea: Peracarida) del Mar Caribe mexicano y Poliquetos pelágicos del Golfo de México y Mar Caribe mexicano (Poliquetos). 132 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 381 records from Collection of symbiotic copepods associated with Caribbean invertebrates. 1 records from A new skipper from China: Notocrypta ariannae n. sp. (Lepidoptera, Hesperiidae). 4 records from Supplement to the knowledge of the genus Batraxis Reitter (Coleoptera: Staphylinidae: Pselaphinae) of China. 5 records from A new species of Loricaria (Siluriformes: Loricariidae) from the Turiaçu River basin, Eastern Amazon region, Brazil. 64 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 133212 records from Arizona State University Hasbrouck Insect Collection. 368 records from Plantas de la expedición en el páramo El Consuelo, Boyacá - Proyecto Boyacá BIO. 199567 records from Vascular plant herbarium TRH, NTNU University Museum. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 3361 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 4 records from A new genus of katydid from the Amazon Rainforest (Orthoptera: Tettigoniidae; Phaneropterinae; Steirodontini): Ninth contribution to the suprageneric organization of the Neotropical phaneropterines. 35 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 1480 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 3400 records from Lista florística de la Costa Grande del estado de Guerrero. 1 records from A new diurnal gecko in the genus Gonatodes (Squamata: Sphaerodactylidae) from Margarita Island, Venezuela. 346 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 179 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 4 records from A new species of Synotaxus and the first chromosomal study on Synotaxidae, presenting a rare XY sex chromosome system in spiders (Araneae, Araneoidea). 1 records from A new species of the genus Gracixalus (Amphibia: Anura: Rhacophoridae) from Mount Jinggang, southeastern China. 4 records from A review of the Callogobius (Teleostei: Gobiidae) from the Red Sea with the description of a new species. 2 records from Ukamenia Oku, 1981 (Lepidoptera: Tortricidae: Olethreutinae), new record for Thailand with descriptions of a new species. 1 records from A new species of genus Oxytauchira from India (Orthoptera: Acrididae). 21 records from Descriptions of a new species and previously unknown males of Nesticus (Araneae: Nesticidae) from caves in Eastern North America, with comments on species rarity. 2 records from Potamonautes nheenae, a new species of freshwater crab from Gabon, Central Africa, with a description of the first known male of Erimetopus brazzae (A. Milne-Edwards, 1886) from the Democratic Republic of the Congo, Central Africa (Brachyura: Potamoidea: Potamonautidae). 46057 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 53 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 2 records from A strikingly coloured new giant millipede from Vietnam has copycat in Borneo (Diplopoda, Spirostreptida, Harpagophoridae). 6 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 225099 records from UF FLMNH Ichthyology. 1 records from West Palaearctic species of the genus Diostracus Loew, 1861 (Diptera: Dolichopodidae). 2 records from Descripción de una nueva especie del grupo Drosophila tripunctata (Diptera: Drosophilidae) en Cruz Loma, Pichincha, Ecuador. 6 records from On two sibling Lathys species (Araneae, Dictynidae) from northern Europe. 23 records from Two new species and new records of terrestrial isopods (Crustacea, Isopoda, Oniscidea) from Brazilian caves. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 21 records from Family groups of Diopsoidea and Nerioidea (Diptera: Schizophora) - Definition, history and relationships. 5 records from Three new species of Ischioscia Verhoeff, 1928 (Isopoda, Oniscidea, Philosciidae) from Serranía de Perijá, Andean Cordillera, Colombian Caribbean. 55 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 1 records from Aloe trinervis sp. nov.: A new succulent species from Indian Desert (Asphodelaceae). 1 records from A new species of tooth-carp, Aphanius mesopotamicus, from Iran and Iraq (Actinopterygii, Cyprinodontidae). 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 2 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 13 records from Deep sea Syllidae (Annelida, Phyllodocida) from Southwestern Atlantic. 17755 records from K-State Museum of Entomological and Prairie Arthropod Research. 15 records from Anfibios y reptiles de la expedición en el cañon medio del Chicamocha, Boyacá - Proyecto Boyacá BIO. 9 records from Description of a new genus and species of Chrysopetalidae (Annelida: Polychaeta) from the NE Atlantic, with some further records of related species. 4 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 92 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 3 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 186 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 942 records from New data on the dragonfly fauna of the Moulouya River Basin and the Oriental Region, Morocco (Odonata). 2 records from A new genus and two new species of arctiine tiger moth (Noctuidae, Arctiinae, Arctiini) from Costa Rica. 171 records from Studies on the Australian Muscidae (Diptera). VIII. The genus Lispe Latreille, 1797. 4 records from Two more new Hemiphyllodactylus Bleeker, 1860 (Squamata: Gekkonidae) from Tamil Nadu, India. 11 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 11724 records from Coleção de Crustacea do Museu Nacional (MNRJ - CARCINO). 2 records from Macedomeris, a new monotypic doderiinine genus (Diplopoda, Glomerida) from a cave in North Macedonia, Balkan Peninsula. 946 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 12 records from A new species of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes: Heptapteridae) from the Orinoco River basin. 12 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 3 records from Taxonomic review of Athliini (Coleoptera: Scarabaeidae: Melolonthinae), a new tribe of scarab beetles endemic to South America. 1 records from Lissotes working-group. 10 records from Laophontodes typicus T. Scott (Copepoda, Harpacticoida, Laophontodinae) - discovering a species complex by morphology. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 1 records from Two new species of the genus Gibbotettix Zheng, 1992 (Orthoptera: Tetrigidae, Cladonotinae) from China. 321 records from Collection Echinodermata SMF. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 45 records from Robert Forsyth Terrestrial Gastropods Collection. 5020 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 72 records from Swedish Malaise Trap Project (SMTP) - Xoridinae. 25 records from Cladistics and revision of Alitocoris with considerations on the phylogeny of the Herrichella clade (Hemiptera, Pentatomidae, Discocephalinae, Ochlerini). 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 63 records from Cethosia myrina butterfly specimens at Museum Zoologi Bogor, Indonesia. 2 records from Two new butterfly species (Lepidoptera: Rhopalocera) from Mount Cameroon, Gulf of Guinea Highlands, Cameroon. 1 records from A new species of the ghost shrimp genus Neocallichirus Sakai, 1988 from Iran, and new record of N. manningi Kazmi & Kazmi, 1992 (Decapoda: Axiidea: Callianassidae). 37928 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 3 records from Two new species of freshwater crabs from the highlands of northern Uganda, East Africa and a redescription of Potamonautes amalerensis (Rathbun, 1935) stat. rev. from Mount Kadam (Brachyura: Potamoidea: Potamonautidae). 3 records from Taxonomy and natural history of the myrmecophilous genus Clinterocera Motschulsky, 1858 (Coleoptera: Scarabaeidae: Cetoniinae) from China and adjacent regions: revision of the C. jucunda species group. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 4 records from A new species of the remarkable brittle star genus Astrophiura (Echinodermata: Ophiuroidea) from the western Atlantic Ocean. 124 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 1 records from Description of a new Gibbaranea (Araneae: Araneidae) from the Western Mediterranean. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 5 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 1 records from A new species of Parafimbrios from northern Vietnam (Squamata: Xenodermatidae). 2126 records from Dolichopodidae of Portugal - dataset 2009-2018. 1914 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 1387 records from Estudio de la diversidad florística de la región de Nizanda en el Istmo de Tehuantepec, Oaxaca. 1 records from A new deepwater gurnard of the genus Pterygotrigla (Scorpaeniformes: Triglidae) from the southwestern Indian Ocean. 45 records from New species, a new combination, and a new country record in American Clytini (Coleoptera: Cerambycidae: Cerambycinae). 16 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 25 records from Plantas en ecosistemas agropecuarios de la quebrada Piedra Candela, en la altillanura plana del Meta. 5 records from Two new species of Eumeninae from Iran (Hymenoptera: Vespidae). 27676 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 3375 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 24 records from Mantidflies (Neuroptera, Mantispidae) from Tocantins state (Brazil): distribution and identification key. 36 records from A review of Spathipheromyia (Diptera: Muscidae) from Argentina with the description of an extra-large new species. 49 records from Historical review, catalog of type specimens and online database of the ichthyology collection of the Instituto de Ciencias Naturales of the Universidad Nacional de Colombia (ICN-MHN). 5 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 2 records from The first species of the pseudoscorpion genus Lechytia Balzan, 1892 (Pseudoscorpiones, Chthoniidae) from New Zealand. 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 2 records from A new species of the genus Mawenzhena Alexis & Delpont (Coleoptera Scarabaeidae: Cetoniinae: Goliathini) from South Korea. 4 records from A review of the feather mite family Gabuciniidae Gaud & Atyeo (Acariformes Astigmata: Pterolichoidea) of Brazil, with descriptions of eleven new species. 2060 records from Flora d'Andorra. 670 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 4 records from Four new earthworm species of Kazimierzus Plisko, 2006 (Clitellata, Kazimierzidae). 84 records from New Mexico Museum of Natural History and Science (NMMNHS) Insect specimens (Arctos). 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 6010 records from Computarización de la colección de insectos de la Universidad de Morelos, CIByC, UAEM. 7 records from A new genus and three new species of nemacheilid loaches from northern Irrawaddy drainage, Myanmar (Teleostei: Cypriniformes). 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 1 records from Erpetogomphus oxybelis sp. nov. from Veracruz, Mexico (Odonata: Gomphidae). 2 records from New fossil genus and new extant species of diatoms (Stephanodiscaceae, Bacillariophyceae) from Pleistocene sediments in the Neotropics (Guatemala, Central America): adaptation to a changing environment?. 5 records from The species of the bee genus Centris of the “ hyptidis group ” revisited with the description of Centris (Anisoctenodes) new subgenus (Hymenoptera: Apidae: Centridini). 1 records from A new species of the genus Paratus Simon (Araneae: Liocranidae) from Thailand. 1901 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 454 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 6 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 5 records from On the new monotypic wolf spider genus Ovia gen. nov. (Araneae: Lycosidae, Lycosinae). 1298 records from Vermont Orthoptera Records from Historic Dot Maps. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 2289 records from Specimen records of spiders (Arachnida: Araneae) by monthly census for 3 years in forest areas of Yakushima Island, Japan. 3927 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 6 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 738 records from Correlación entre las condiciones ambientales y la pesquería de anchoveta a lo largo de la costa de Baja California. 6661 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 6566 records from CABI Lepidoptera Collection. 8 records from Two new and potentially highly threatened Megophrys Horned frogs (Amphibia: Megophryidae) from Indochina’s highest mountains. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 2 records from Two new species of Sympagella (Porifera: Hexactinellida: Rossellidae) collected from the Clarion-Clipperton Zone, East Pacific. 123941 records from University of Guelph Insect Collection (DEBU). 4 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 7 records from New species of Culex (Culiciomyia) (Diptera: Culicidae) from Talangaye Forest in Cameroon and descriptions and identification keys for males of the Afrotropical species of the subgenus. 95 records from Marine algal (seaweed) flora of Faial Island, Azores. 1 records from Revision and redefinition of the crematogastrine ant genus Tetheamyrma BOLTON, 1991, with the description of a new species and the first description of the dealate queen (Hymenoptera: Formicidae). 3126 records from Solitary bees collected in a large-scale field experiment in power line clearings, southeast Norway. 6 records from Redescription and new records of a poorly known leucosiid crab, Pseudophilyra punctulata Chen & Ng, 2003, and description of a new species of Pseudophilyra from Japan (Crustacea: Decapoda: Brachyura). 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 809 records from ant-plant_symbioses. 1 records from Epimecia tekes, a new species from south-eastern Kazakhstan (Lepidoptera Noctuidae, Oncocnemidinae). 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 1 records from Overview of bat species reported in Albania with the first country records for eight species. 4 records from Herbarium Senckenbergianum (FR) - Protista. 1 records from Colección de Zoología Invertebrados - Carcinología. 1 records from The mature larva and pupa of Tychius subsulcatus Tournier, 1847 (Coleoptera, Curculionidae), with comments on its biology and phylogenetic relationships. 1 records from The neotropical genus Sporrongia Gumovsky (Hymenoptera: Eulophidae) including two new species and the first biological record. 1625 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 20 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 46 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 13 records from Five new species of Stenochrus (Schizomida: Hubbardiidae) from Oaxaca, Mexico. 1 records from Two new eriophyoid mite species (Trombidiformes: Eriophyoidea) from the cocoa tree, and a note on Shevtchenkella biseta (Nalepa). 248 records from Taxonomy and distribution of pimpline parasitoids (Hymenoptera, Ichneumonidae, Pimplinae) in Ukraine. 7377 records from NEON Biorepository Mammal Collection (Hair Samples). 3309 records from Base de datos del Municipio General Heliodoro Castillo, Guerrero (120. Sierra Madre del Sur). 4389 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 1 records from New species and new record of Thraulodes Ulmer, 1920 (Ephemeroptera: Leptophlebiidae: Atalophlebiinae) from Brazil. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 5 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 677 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 24 records from Vermont Oil Beetle Records from Pinto and Selander 1970. 100 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 2 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 197 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 203 records from Echinoderms from the Seaflower Biosphere Reserve. 3 records from The first Nearctic record of the genus Neocheiridium (Pseudoscorpiones: Cheiridiidae), with description of Neocheiridium gullahorum sp. n.. 3 records from A review of the genera Anasillomos Londt, 1983, Oratostylum Ricardo, 1925, and Remotomyia Londt, 1983, with description of a new genus and two new species (Diptera: Asilidae: Stenopogoninae). 2 records from A new species of Oryttus Spinola, 1836 from the United Arab Emirates and Tunisia with identification key to Palaearctic species (Hymenoptera, Crabronidae). 1322 records from EVB herbarium - Herbário Evaldo Buttura - Herbário Virtual REFLORA. 24 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 182252 records from Allan Herbarium (CHR). 57023 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from A novel member of the Hemidactylus brookii complex (Squamata: Gekkonidae) from the Western Ghats of Maharashtra, India. 1 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 24 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 3634 records from Fungal Collection of Natural History Museum and Institute, Chiba. 2 records from Tomoceridae (Collembola, Entomobryomorpha) from the southern Annamitic cordillera: redescription of Tomocerus ocreatus Denis, 1948 and description of a new species of Tomocerina Yosii, 1955. 14275 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 16 records from Two new sympatric species of Stenocercus (Squamata: Iguania) from the inter- Andean valley of the Mantaro River, Peru. 8 records from Review of the genus Typhloiulus Latzel, 1884 in the Dinaric region, with a description of four new species and the first description of the male of Typhloiulus insularis Strasser, 1938 (Diplopoda: Julida: Julidae). 1124 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 4 records from Nomenclatural changes in American Apomecynini including description of new genera and species (Coleoptera: Cerambycidae). 1 records from MVZ Herp Observations (Arctos). 4 records from First record of Psilacrum Becker 1912 (Chloropidae, Diptera) from Brazil, with the description of a new species. 20472 records from Cercle des mycologues de Montréal Fungarium (CMMF). 10 records from A new stiletto fly genus from South America (Diptera: Therevidae: Agapophytinae). 1 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 27 records from New records in vascular plants alien to Kyrgyzstan. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 4 records from A new species of Stasimopus from the Eastern Cape Province of South Africa (Araneae, Mygalomorphae, Ctenizidae), with notes on its natural history. 1 records from Chenopodium vulvaria. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 6 records from The genus Ctenomelynthus (Hemiptera: Heteroptera: Coreidae: Acanthocephalini), with the description of three new species and key to the known species. 42 records from Contribution to the knowledge of the earthworm fauna of Turkey with description of three new species (Clitellata: Megadrili). 100 records from Estudio de la variabilidad genética de Fundulus lima y sus relaciones filogeográficas con otros fundúlidos (Pisces: Fundulidae) de la Península de Baja California, México. 2 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 1 records from Two new Afrotropical genera of Scatopsidae (Diptera). 846 records from PAMP-tracheo: Vascular plants in La Demanda and Cameros mountain ranges (La Rioja, Spain). PhD project, L.M. Medrano. 3689 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 2 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 7 records from Taxonomic study of the genus Hypatopa Walsingham, 1907 (Lepidoptera: Blastobasidae) in China, with descriptions of five new species. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009 (Región golfo centro). 176 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 4 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 2 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 3 records from Contribution to the knowledge of Dialeurodes (Gigaleurodes) Quaintance & Baker (Hemiptera: Aleyrodidae), with description of a new species from China. 190 records from NEON Biorepository Benthic Macroinvertebrate Collection (DNA Extracts). 8 records from Taxonomic revision of Plyomydas Wilcox & Papavero, 1971 with the description of two new species and its transfer to Mydinae (Insecta: Diptera: Mydidae). 3 records from Vietelmis jablonskii, a new species of riffle beetle from Laos and Thailand and new faunistic records on Vietelmis Delève, 1968 from Malaysia (Coleoptera: Elmidae). 4 records from A new black fly species of Simulium (Simulium) (Diptera: Simuliidae) from Taiwan. 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 3 records from A new Antillobisium species (Arachnida: Pseudoscorpiones: Bochicidae) from Cuba, with biogeographical and ecological remarks on the genus. 2 records from A new species of the genus Hebius (Squamata: Colubridae: Natricinae) from Hunan Province, China. 7 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 1139 records from SWECO. 1552 records from Mollusk Collection of Yokosuka City Museum. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 2321 records from Dataset of fungus gnats (Diptera,Sciaroidea) from Møre og Romsdal county in Norway. 16556 records from EAC - Herbário Prisco Bezerra. 3 records from Systematics of Helioandesia tarregai gen. et sp. nov. (Lepidoptera: Yponomeutoidea: Heliodinidae) from the Andes of Northern Chile. 8006 records from Knerer collection / Gschwendtner property. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1531 records from Leif Richardson Vermont Bee Specimens. 63 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 2 records from Family Rhinolophidae. Horseshoe Bats in Checklist of African Mammals. 9339 records from Collection Crustacea - ZMB. 2 records from New data on the taxonomy, ecology, and conservation of the rediscovered Louisea edeaensis (Bott, 1969) (Brachyura: Potamoidea: Potamonautidae), an endangered freshwater crab from Cameroon. 1 records from A new long-legged terrestrial freshwater crab, Calcipotamon puglabrum gen. nov et sp. nov. (Crustacea: Decapoda: Potamidae), from Hainan Island, China. 724 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 4 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 1034 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 1 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 19 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 1 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from Description of a new genus and four new species of Acaricalini (Acari, Eriophyidae, Phyllocoptinae) from South China. 1 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 1 records from On Starengovia Snegovaya, a genus of Asian nemastomatines (Arachnida: Opiliones: Nemastomatidae). 8 records from Polycentropus dinkinsorum (Trichoptera: Polycentropodidae), a newly described caddisfly species from the southern Appalachian Mountains, USA. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 1 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 143 records from Dermaptera in the icipe collection. 1248 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 1 records from A new genus and species of Ingolfiellidae (Crustacea, Ingolfiellida) from the hyporheic zone in the Sierra de la Ventana, and its biogeographic relevance. 25 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 13503 records from MVZ Egg and Nest Collection (Arctos). 29 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 18 records from Overvåking Røsskleiva NR. 3 records from A new species of the genus Morimotanthribus Senoh & Trýzna (Coleoptera Anthribidae) from South China. 10 records from A new genus and species of cricket from eastern Cuba: the first Antillean true Eneopterinae (Orthoptera: Gryllidae: Eneopterinae). 1 records from New collections of freshwater crabs from northern Madagascar, with the description of a new species of Foza Reed & Cumberlidge, 2006 (Brachyura, Potamonautidae), and comments on their conservation status. 4 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 4040 records from Herbario Enrique Forero de la Universidad de la Amazonia (HUAZ). 4 records from Four new species of Rhyacophila Pictet 1834 (Trichoptera: Rhyacophilidae) from Southeast Asia. 6 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 2 records from Naturalis Biodiversity Center (NL) - Orthopteroidea. 89 records from Dragonflies (Odonata) From The Sierras Of Tapirapeco And Unturan, In The Extreme South Of Venezuela. 7 records from Taxonomy and evolution of asymmetric male genitalia in the subgenus Ashima Chen (Diptera: Drosophilidae: Phortica Schiner), with descriptions of seven new species. 7143 records from MCP-Anfibios - Coleção de Anfíbios. 1 records from A new and likely extinct species of Antilissus Sharp, 1879 (Coleoptera: Zopheridae Colydiinae) from Makauwahi Cave, Kauai, Hawaiian Islands. 7 records from Deep into darkness: the first stygobitic species of freshwater shrimp of the genus Caridina (Crustacea: Decapoda: Atyidae) from Northern Vietnam. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 367 records from Coleção de Mamíferos da Universidade Estadual do Norte Fluminense. 3 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 18540 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 63754 records from E. C. Smith Herbarium (ACAD). 1 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 1750 records from Colección del Herbario de la Universidad de los Llanos. 1057 records from Hongos ectomicorrizógenos y myxomycetes asociados con Picea chihuahuana en la Sierra Tarahumara. 7 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 1 records from New species, redescriptions and phylogenetic revision of tribe Dacini (Diptera: Tephritidae: Dacinae) from India based on morphological characters. 1711 records from KTU Pinophyta. 11686 records from NCSM Mammalogy Collection. 15 records from Review of the genus Trichactia Stein (Diptera: Tachinidae) in the Palaearctic Region, with the description of a new species from Iran and the East Mediterranean. 24 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 17721 records from HCF herbarium - Universidade Tecnológica Federal do Paraná - Campus Campo Mourão - Herbário Virtual REFLORA. 2 records from Notes on Malagasy Discheramocephalus Johnson (Coleoptera: Ptiliidae). 20 records from A revision of the Patagonian predaceous midges of the subgenus Acanthohelea of Stilobezzia excluding the S. (A.) edwardsi group (Diptera: Ceratopogonidae). 101 records from Fungal Bioblitz in Białowieża Primeval Forest at 18th Congress of European Mycologists. 91645 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 3 records from A new species of Arrhopalites Börner, 1906 (Collembola, Symphypleona, Arrhopalitidae) from Iran with an updated key to A. diversus group of species. 7 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 4 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 3 records from Two new cavernicolous Pselaphinae (Coleoptera: Staphylinidae) from southern China. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 3 records from A peculiar new species of the genus Grammacephalus Haupt (Hemiptera Auchenorrhyncha: Cicadellidae: Deltocephalinae) from Madagascar. 8997 records from Insect specimens of Toyota City Nature Sanctuary. 165 records from Nine new species of Enithares (Heteroptera: Notonectidae) from New Guinea, with distributional notes on other species and an updated world checklist. 6 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 17 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 3 records from Eleven new species and a new country record of Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) from China, with a revised checklist of world species. 4207 records from CASES2003_2004. 15 records from Pelagic ctenophores from the São Sebastião Channel, southeastern Brazil. 376 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Xiloteca). 124 records from North Marine Region whaler shark collection records (DEW collation), Australia (1999- 2005). 30 records from Two new species of Odontostilbe historically hidden under O. microcephala (Characiformes: Cheirodontinae). 570 records from Flora ficológica marina de Tamaulipas. 7273 records from Vascular plants collection of Hiratsuka City Museum. 53 records from CHAS Botany Collection (Arctos). 10 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 3006 records from Plantas de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 398 records from Mammal specimens of Kawasaki Municipal Science Museum. 7 records from A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan. 1462 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 21 records from Hyolithen - SMF. 7 records from The genus Stactobiella Martynov (Trichoptera, Hydroptilidae) in Japan. 79 records from Marine algal (seaweed) flora of São Jorge Island, Azores. 4 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 2 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 136 records from Three new species, Elathous zagrosensis sp. n., Zorochros dilatatus sp. n., and Dicronychus iranicus sp. n., and noteworthy records of click beetles from western Iran (Coleoptera: Elateridae). 1 records from Coarazuphium lundi (Carabidae: Zuphiini), a new Brazilian troglobitic beetle with the designation of a neotype for C. pains Álvares & Ferreira, 2002. 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 2 records from Two new species of the Rhyacophila nigrocephala species group from China (Insecta, Trichoptera, Rhyacophilidae). 2 records from A new species of the genus Oligodon Fitzinger, 1826 (Squamata: Colubridae) from Cu Lao Cham Islands, central Vietnam. 23 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 1 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 32 records from Barsura Volynkin, Dubatolov & Kishida, gen. nov., with descriptions of three new species (Lepidoptera, Erebidae, Arctiinae). 4 records from A review of the genus Trachystolodes Breuning, 1943 (Coleoptera: Cerambycidae Lamiinae: Lamiini). 11994 records from Hatikka Observation Database. 2493 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 48 records from Porifera MZS. 1 records from Herpetology. 2 records from A new groundwater-dwelling species of Euryrhynchina from Cameroon (Malacostraca, Decapoda, Euryrhynchidae). 337 records from OSAC North American Cossoidea -beta version. 16 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 8 records from Modelaje de la distribución potencial de 10 especies de anfibios y reptiles en riesgo de extinción con escasos registros de presencia (LEPMIC). 4 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 11 records from A survey of East Palaearctic Gnaphosidae (Araneae). 5. On Synaphosus from Central Asia. 80 records from DNA Barcoding and Integrative Taxonomy of the Heterolepisma sclerophylla species complex (Zygentoma: Lepismatidae: Heterolepismatinae) and the Description of Two New Species. 1 records from A new species of Acanthosaura Gray 1831 (Reptilia: Agamidae) from central Vietnam. 1 records from A new species in the Trachusa ovata species group (Hymenoptera: Apoidea) from Peninsular Malaysia with an overview of the old-world species within the genus Trachusa. 219 records from Banco de Germoplasma Vegetal del Jardín Botánico de Olarizu (Vitoria-Gasteiz)/Olarizuko Lorategi Botanikoaren Landare Germoplasma Bankua (Vitoria-Gasteiz). 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 4 records from Cliona acephala (Porifera: Demospongiae: Clionaida), a new encrusting excavating reef sponge from the Colombian Caribbean belonging to the Cliona viridis species complex. 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 298 records from New data on species diversity of Annelida (Oligochaeta, Hirudinea) in the Kharbey lakes system, Bolshezemelskaya tundra (Russia). 129 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 5 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 9 records from New species and stages description of Traverella Edmunds, 1948 (Ephemeroptera Leptophlebiidae) from Northeast Brazil. 4 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 5501 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 9650 records from Herbario de Universidad de Murcia: MUB. 655877 records from NSW AVH data. 463 records from Revisión de las Agavaceae (sensu stricto), Crassulaceae y Liliaceae incluidas en el PROY-NOM-059-ECOL-2000. 3 records from Parochodaeus bituberculatus (Erichson) (Coleoptera: Ochodaeidae) and Faargia gentilii (Martínez) (Coleoptera: Scarabaeidae), two species newly discovered in Chile. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 1297 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 2 records from A new species of Pasiphaea Savigny, 1816 (Crustacea, Decapoda, Pasiphaeidae) from the southwestern Atlantic. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 2 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 10075 records from Nematoda of Costa Rica (INBio). 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 1 records from DNA barcodes and morphology confirm a new species of Rheocricotopus (Psilocricotopus) orientalis group (Diptera: Chironomidae). 682 records from Towson University - MidAtlantic - Ailanthus altissima - 2011. 18 records from Two new species of Curculionichthys (Siluriformes: Loricariidae) from the rio Amazonas basin, Brazil. 4 records from Two more new species of the Cyrtodactylus peguensis group (Squamata: Gekkonidae) from the fringes of the Ayeyarwady Basin, Myanmar. 552 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 7359 records from Crustaceos del Museo de Ciencias naturales de la Universidad Simón Bolívar. 332732 records from South Australian Museum Australia provider for OZCAM. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 2 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 1 records from A new species of Tapiena (Orthoptera: Tettigonioidea: Phaneropterinae) from Brunei Darussalam (Borneo, Southeast Asia). 12 records from Three new ghost moths of the genus Oxycanus Walker, 1856 from Australia (Lepidoptera: Hepialidae). 1514 records from Colección de Polypodiales, Proteales, Psilotales y Ranunculales del Museo Botánico CORD - IMBIV. 386 records from MGC Herbarium of University of Malaga (Spain): MGC-Briof dataset. 11 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 100 records from Brock University Herbarium (BU). 12 records from Descriptions of eight new species of the genus Parancistrocerus Bequaert (Hymenoptera: Vespidae: Eumeninae), with a key to the Oriental species. 249 records from Georgian Academy of Sciences, Institute of Botany, National Herbarium of Georgia. 23 records from Five species of the genus Epicephala Meyrick, 1880 (Lepidoptera: Gracillariidae) from China. 3105 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Cryptogamic National Collection (BAc). 9 records from Three new species of earthworms (Oligochaeta: Megascolecidae) from Yunnan Province, China. 998 records from Invasive Alien plant species of Malawi. 1 records from Haruchlora maesi, a new emerald moth genus and species from Mesoamerica (Lepidoptera, Geometridae, Geometrinae). 2 records from Colaphellus palaestinus Achard, a new leaf-beetle for Europe (Coleoptera, Chrysomelidae, Chrysomelinae). 10 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 97 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 2 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 4 records from Redescription of Alopecosa albostriata (Araneae: Lycosidae) based on specimens from Siberia. 2 records from The genus Eodendrus Belokobylskij (Hymenoptera, Braconidae, Doryctinae) from China, with description of a new species. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 2 records from Genetic and morphological evidence for a new cryptic species of Ectinogonia (Coleoptera: Buprestidae) from central Chile. 85 records from Benthic Polychaeta (Annelida) from La Paz Bay and Southwestern Gulf of California. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 38 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 155 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 17 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 160047 records from Swiss National Mollusca Databank. 6 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 6 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 1 records from Genetic and morphological evidence for cryptic species in Macrobrachium australe and resurrection of M. ustulatum (Crustacea, Palaemonidae). 1218 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 1 records from A large hornet mimic clearwing moth of the genus Lamellisphecia Kallies & Arita 2004 (Lepidoptera, Sesiidae) from Nanling, Guangdong, southern China. 669 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 2988 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 1 records from A new species of Merothrips from the Dampa Tiger Reserve, Mizoram, India (Thysanoptera, Terebrantia). 1 records from Beyond shells: first detailed morphological description of the mangrove-associated gastropod Haminoea cf. fusca (A. Adams, 1850) (Cephalaspidea, Haminoeidae), with a COI phylogenetic analysis. 12 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 26 records from Collection Lepidoptera SMF. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 1 records from A new species of alpheid shrimp tentatively assigned to Salmoneus Holthuis, 1955 (Decapoda: Caridea) from the Ryukyu Islands, Japan. 93662 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 13 records from Review of Poecilimon species with inflated pronotum: description of four new taxa within an acoustically diverse group. 83 records from Mexican species of the genus Orthocentrus (Hymenoptera, Ichneumonidae: Orthocentrinae). 36 records from University of Sindh Jamshoro Herbarium. 1254 records from Bryozoa, Brachiopoda and Entoprocta from the collection of the Arctic University Museum of Norway in Tromsø. 8 records from Disentangling vines: a study of morphological crypsis and genetic divergence in vine snakes (Squamata: Colubridae: Ahaetulla) with the description of five new species from Peninsular India. 29 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 5 records from The Apseudomorpha (Crustacea: Tanaidacea) of the Gulf of Cadiz and Horseshoe Continental Rise (NE Atlantic): A taxonomic review with new records, species, and ecological data. 1 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 62 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 3 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 2 records from Revision of Taurocerus (Heteroptera, Pentatomidae, Pentatomini). 2 records from A new genus of Pharaxonothinae from Australia (Coleoptera: Erotylidae). 13 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 4 records from Two new species of Atlantoscia Ferrara & Taiti, 1981 (Isopoda: Oniscidea: Philosciidae) from southern Brazil described in the light of integrative taxonomy. 5 records from Two new species of Paratanytarsus Thienemann & Bause (Diptera: Chironomidae) from Oriental China. 2 records from Two new species of the genus Atractoscion, and resurrection of the species Atractoscion atelodus (Günther 1867) (Perciformes: Sciaenidae). 3 records from Flightless Catapionus (Coleoptera: Curculionidae: Entiminae) in Southwest China survive the Holocene trapped on mountaintops: new species, unknown phylogeny and clogging taxonomy. 7 records from New endemic species of freshwater crayfish Parastacus Huxley, 1879 (Crustacea: Decapoda: Parastacidae) from the Atlantic forest in southern Brazil. 6 records from A new species of turtle-headed sea Snake (Emydocephalus: Elapidae) endemic to Western Australia. 6 records from Systematics of New Guinea treefrogs (Litoria: Pelodryadidae) with erectile rostral spikes: an extended description of Litoria pronimia and a new species from the Foja Mountains. 3 records from A name for the nurse-frog (Allobates, Aromobatidae) of Floresta Nacional de Carajás, Eastern Brazilian Amazonia. 2 records from Description of female of Titidius urucu Esmerio & Lise, 1996 (Araneae: Thomisidae). 35 records from Revision of the stygobiont gastropod genera Plagigeyeria Tomlin, 1930 and Travunijana Grego & Glöer, 2019 (Mollusca; Gastropoda; Moitessieriidae and Hydrobiidae) in Hercegovina and adjacent regions. 12 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 1 records from Systematic revision of Central American Calligrapha Chevrolat of the subgenus Erythrographa subgen. nov. (Coleoptera: Chrysomelidae, Chrysomelinae). 7010 records from La familia Asclepiadaceae en México. 3 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 8 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 70 records from Swedish Malaise Trap Project (SMTP) - Odonata. 1 records from New species of Raphidascaris (Sprentascaris) (Nematoda: Anisakidae) in Rineloricaria steinbachi (Actinopterygii: Loricariidae) from Northwest Argentina. 1 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 26 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 4 records from A new species of small and highly abbreviated caecilian (Gymnophiona: Indotyphlidae) from the Seychelles island of Praslin, and a recharacterization of Hypogeophis brevis Boulenger, 1911. 126388 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 15 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 17 records from Cellaria (Bryozoa, Cheilostomata) from the deep: new species from the southern Zealandian region. 1029 records from Collembola of spruce forests of Kola Peninsula. 2402 records from Platynotina (Coleoptera: Tenebrionidae) collections on the World. 2 records from Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China. 5 records from The Stenus cirrus group (Coleoptera, Staphylinidae) in Fujian, East China. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 38 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 13 records from Seven new species of Loneura Navás (Insecta: Psocodea: ‘ Psocoptera’: Ptiloneuridae) from Valle del Cauca, Colombia. 57973 records from Mammals Specimens. 1 records from Two new species of the genus Metaxonchium Coomans & Nair, 1975 (Nematoda, Dorylaimida, Belondiridae) from Vietnam. 89 records from SIM-XII Jornadas Micológicas El Ilustre Minero. 4 records from Two new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from Guizhou and Guangxi, China. 1 records from First record of spongillaflies (Neuroptera: Sisyridae) from Colombia. 1283 records from Lauri Mällo private collection of Lepidoptera. 3 records from Review of the Swedish Enicospilus (Hymenoptera; Ichneumonidae; Ophioninae) with description of three new species and an illustrated key to species. 1 records from A new species and new record of Polycystididae (Rhabdocoela: Kalyptorhynchia) from China. 22771 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 87 records from Dichomeris Hübner, 1818 (Lepidoptera, Gelechiidae, Dichomeridinae) from Cambodia, including associated Chinese species. 2 records from Glasgow Museums BRC: Chrysomelidae. 3 records from A new species-group with new species of the genus Lasioseius (Acari: Mesostigmata: Blattisociidae) associated with Neotropical hispine beetles in furled leaves ofHeliconia. 274 records from 2019-KNAM-PL. 4 records from Carnivorous sponges (Porifera, Cladorhizidae) from the deep South Pacific (New Caledonia) with the description of three new species of the genus Abyssocladia and remarks on genus Cercicladia. 13 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 897 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 118 records from Taxonomy and host-plant relationships of the psyllid genus Mitrapsylla (Hemiptera: Psylloidea: Psyllidae) in Brazil. 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 8423 records from University Of Pretoria: Lacewing Database Project (1911-2015). 7 records from Paraorosius, a new genus of leafhopper (Hemiptera: Cicadellidae: Deltocephalinae: Opsiini), with description of a new species from the Middle East. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 3277 records from USAC Mammals Collection. 4288 records from New Zealand Biodiversity Recording Network. 3 records from A new species of the genus Colilodion Besuchet, 1991 (Coleoptera: Staphylinidae: Pselaphinae) from Mindanao, the Philippines. 46 records from Unexpected diversity of the genus Collarina Jullien, 1886 (Bryozoa, Cheilostomatida) in the NE Atlantic-Mediterranean region: new species and reappraisal of C. balzaci (Audouin, 1826) and C. fayalensis Harmelin, 1978. 1 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 3350 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 2488 records from SMNS Herpetologie. 32 records from The jumping plant-lice of the Neotropical genus Tainarys (Hemiptera: Psylloidea) associated with Anacardiaceae. 4 records from A new species of Ergasilus von Nordmann, 1832 (Copepoda: Cyclopoida) from the gills of a dasyatid ray, Himantura oxyrhyncha (Sauvage, 1878) from West Kalimantan, Indonesia. 23 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 2 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 788 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 1402 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 7 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 5 records from Morphological description and DNA barcoding of Hydrobaenus laticaudus Saether 1976 (Diptera: Chironomidae: Orthocladiinae) from Amur River basin (Russian Far East). 1261 records from Synopsis of Schizanthus: list of specimens examined. 1 records from Taxonomy of some Galeommatoidea (Mollusca, Bivalvia) associated with deep-sea echinoids: A reassessment of the bivalve genera Axinodon Verrill & Bush, 1898 and Kelliola Dall, 1899 with descriptions of new genera Syssitomya gen. nov. and Ptilomyax gen. nov.. 21 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 3 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 6 records from Four new species of Scydmaeninae and Pselaphinae (Coleoptera: Staphylinidae) from Yunnan, China. 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 1 records from A new species of frog in the Litoria ewingii species group (Anura: Pelodryadidae) from south-eastern Australia. 1 records from Adamastoraltica humicola, new genus and new species: the first example of possible moss-inhabiting flea beetle genus from sub-Saharan Africa (Coleoptera Chrysomelidae, Galerucinae). 3 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 87 records from Levinsenia species (Annelida: Polychaeta: Paraonidae) from the Sea of Marmara with descriptions of two new species. 11 records from A new species of Laurenceomyia Wagner & Stuckenberg, with a key to species and new records for Psychodidae (Diptera) from Uruguay. 822 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 19 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 54 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 222 records from The spider family Micropholcommatidae (Arachnida: Araneae: Araneoidea): a relimitation and revision at the generic level. 11121 records from Distribución potencial en taxones hiperdiversos y poco conocidos (Insecta: Coleoptera: Scarabaeoidea): estimando la localización de nuevos taxones y el efecto de los cambios en los usos del suelo. 6782 records from Odonata de Veracruz. 326 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 65 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 1 records from Review of the genus Suwallia (Plecoptera: Chloroperlidae) from China with description of Suwallia jihuae sp. nov. from Sichuan Province. 2112490 records from The CPR Survey. 6 records from The water striders (Hemiptera: Heteroptera: Gerridae) of Costa Rica: new species, checklist, and new records. 37 records from Two new species of Tipula (Vestiplex) Bezzi (Diptera, Tipulidae) from Northwest China. 2423 records from UFRN-Fungos - Herbário UFRN - Fungos. 72563 records from Colección Herbario Federico Medem Bogotá - FMB. 1 records from Species of Macrostomum (Macrostomorpha: Macrostomidae) from the coastal region of Lima, Peru, with comments on M. rostratum Papi, 1951. 33 records from New records of snail-killing flies (diptera: Sciomyzidae) from Iran. 3 records from Three squat lobsters (Crustacea: Decapoda: Anomura) from tropical West Pacific seamounts, with description of a new species of Uroptychus Henderson, 1888. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 35 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 111 records from Andrena cyanura Cockerell, a valid North American species. 5 records from Two new species of the genus Leeonychiurus Sun & Arbea, 2014 (Collembola: Onychiuridae) from Korea. 3662 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 1422 records from Reconocimiento de la biodiversidad de la Reserva de la Biósfera Calakmul: Odonata, psocóptera y díptera acuáticos (Insecta). 10 records from Corynoneura Winnertz (Diptera, Chironomidae, Orthocladiinae) from Zhejiang Province, China. 4 records from A new genus and new species of the leafhopper tribe Idiocerini (Hemiptera Cicadellidae: Eurymelinae). 5 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 363 records from The South American spider genera Mesabolivar and Carapoia (Araneae, Pholcidae): new species and a framework for redrawing generic limits. 11 records from Collection Ephemeroptera - SMF. 1523 records from Vietnamese Bryophyte Collection in Eger Herbarium (EGR). 242 records from FBIP: Identification of polychaetes used as bait. 97757 records from Denver Museum of Nature & Science - Entomology. 3 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 24 records from Onysius Broun: The First New Zealand Genus Of Promecheilidae (Coleoptera: Tenebrionoidea). 3276325 records from Insecta of Costa Rica (INBio). 2 records from A new species of the genus Rapturella (Gastropoda: Acteonidae) from southeast Brazil. 5 records from Four new species of the leafhopper genus Riseveinus Li (Hemiptera: Cicadellidae: Evacanthinae) from China and Thailand. 14557 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 8 records from A review of the Barbatula loaches (Teleostei: Nemacheilidae) from north-eastern China, with the description of four new species. 160 records from Evaluación y monitoreo de manglar en la Reserva de la Biósfera Los Petenes con énfasis en criterios de sustentabilidad y desarrollo. 18 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 1 records from A new Schistura from an upper Mekong affluent in Yunnan (Teleostei: Nemacheilidae). 66 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 2 records from A pilot phylogeny study of Nemobiinae inferred from 18 S, 28 S and genes, with descriptions of two new genera and a new species from Hainan, China (Orthoptera: Grylloidea: Trigonidiidae). 1335 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 4420 records from Actualización e incremento del banco de datos de la colección de herbario del Jardín Etnobotánico de Oaxaca. 1683 records from Collection of Hymenoptera. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 284 records from Berlin-Brandenburg Plant Collection 2006. 7 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 5 records from Studies in Liocranidae (Araneae): redescriptions and transfers in Apostenus Westring and Brachyanillus Simon, as well as description of a new genus. 3673 records from Spider (NSMK-SP). 4179 records from OUPR - Herbário "Professor José Badini". 13308 records from Colección de Asterales del Museo Botánico CORD. 1 records from On several species of Oswaldella Stechow, 1919 (Cnidaria, Hydrozoa), including the description of a new species. 17 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 334 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 568 records from NZCS Invertebrates Old Collection Before 1987. 28 records from Brentidae Acratini du massif du Mitaraka, en Guyane: une synthèse des données (Insecta, Coleoptera, Curculionoidea). 2 records from A new centipede Schendylops Cook from eastern Brazil: the first troglobitic geophilomorph for South America (Geophilomorpha, Schendylidae). 3 records from Hiding in plain sight on Gunung Muria: A new species and first record of rock gecko (Cnemaspis Strauch, 1887; Squamata, Gekkonidae) from Java, Indonesia. 10631 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 1 records from Two new species of Corynellus Bates, 1885 (Coleoptera: Cerambycidae: Cerambycinae). 202 records from The InBIO Barcoding Initiative Database: Diptera 01. 2 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 4 records from First records of Dentridactylinae (Orthoptera: Tridactylidae) from Colombia, with description of two new species of Dentridactylus Günther. 1229 records from Insect Collection (CeStuBio). 5 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 2 records from A new species of Yllenus Simon, 1868 from northern India (Araneae, Salticidae). 54 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 5 records from A new species of Hedya Hübner from Iran with proposed rearrangement of some species currently assigned to Metendothenia Diakonoff (Lepidoptera: Tortricidae). 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 9 records from Swedish Malaise Trap Project (SMTP) - Bethylidae. 5 records from The genus Enicospilus Stephens, 1835 (Hymenoptera, Ichneumonidae, Ophioninae) in Saudi Arabia, with twelve new species records and the description of five new species. 54 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 4 records from A new species of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes Heptapteridae) from the Sierra Nevada de Santa Marta, Colombia. 7 records from Two new species of the genus Apsidophora Diakonoff, 1973 (Lepidoptera Tortricidae: Olethreutinae) from Thailand. 1872 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 16 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Aves (MG-ZV-A). 3918 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 1005 records from Flora vascular de Torca, Localidad de Usaquén (Bogotá - Colombia). 20 records from Subspecies of Pleurota bicostella (Clerck, 1759) revisited and descriptions of nine new species in the P. bicostella species group (Lepidoptera: Gelechioidea Oecophoridae: Pleurotinae). 1 records from The identity of Parandra laevis Latreille, 1804 and nomenclatural changes in the Parandrinae (Coleoptera, Cerambycidae). 1 records from Two new genera and species of Fidicinini Distant, 1905 with a re-description of Nosola Stål, 1866 (Hemiptera, Auchenorrhyncha, Cicadidae). 1 records from World catalogue of the Hydrophiloidea (Coleoptera): additions and corrections II (2006 - 2010). 7 records from Unraveling Ocyptamus and the Baccha legacy (Diptera: Syrphidae): redefinition of groups and new species descriptions. 18 records from Morphologische Daten von Natrix. 3 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 2 records from New state and island records of Coccinellidae (Coleoptera) in Hawai‘i, USA. 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 46 records from Revision of the Garra species of the Hajar Mountains in Oman and the United Arab Emirates with the description of two new species (Teleostei: Cyprinidae). 103 records from Collection botanique Lamy de la Chapelle E. (BOUM). 12457 records from Brown University Herbarium. 214396 records from Mississippi Entomological Museum. 277 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 6 records from The spiny theridiid genus Meotipa Simon, 1895 in India, with description of a strange new species with translucent abdomen and a phylogenetic analysis about the genus placement (Araneae, Theridiidae). 1 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 23 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 17 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 40 records from On the taxonomy of southern South American species of the wolf spider genus Allocosa (Araneae: Lycosidae: Allocosinae). 1 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 58 records from LISU Herbario Angola. 2 records from Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq. 2 records from Chrysobothris bimaculata (Coleoptera: Buprestidae), a new species from Jamaica, with a key to the genus in Jamaica. 74313 records from AM: Freshwater Invertebrates (1900-2005). 1305 records from The Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from A new genus of Hoplojassini from French Guiana (Hemiptera: Cicadellidae Iassinae) and identification key for species of tribe. 52 records from Palaearctic Osmia bees of the subgenera Hemiosmia, Tergosmia and Erythrosmia (Megachilidae, Osmiini): biology, taxonomy and key to species. 136 records from Swedish Malaise Trap Project (SMTP) - Heloridae. 7416 records from Tropical epiphyte diversity under human impact ? Comparing primary forests, secondary forests, and forest fragments in Ecuador - Otonga. 10 records from An inordinate fondness for Osedax (Siboglinidae: Annelida): Fourteen new species of bone worms from California. 2 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 179 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 13 records from Exoasota pursatensis Ko & Bae, new genus and species of the Spilomelinae (Lepidoptera: Pyraloidea: Crambidae) from Indochina. 145 records from BioAcoustica: Wildlife Sounds Database. 12 records from A mountain of millipedes I: An endemic species-group of the genus Chaleponcus Attems, 1914, from the Udzungwa Mountains, Tanzania (Diplopoda, Spirostreptida, Odontopygidae). 8 records from The millipede genus Tylopus Jeekel, 1968 (Diplopoda, Polydesmida, Paradoxosomatidae), with a key and descriptions of eight new species from Indochina. 299 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 4 records from Troglocaris (Xiphocaridinella) kumistavi sp. nov., a new species of stygobiotic atyid shrimp (Crustacea: Decapoda: Atyidae) from Kumistavi Cave, Imereti, Western Georgia, Caucasus. 2 records from Revision of Pleuroprion zur Strassen, 1903 (Holidoteidae) and re-evaluation of Spectrarcturus Schultz, 1981 (Arcturidae) (Crustacea, Isopoda, Valvifera). 80 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 27561 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 3 records from Cylindroniscus platoi (Isopoda: Oniscidea: Styloniscidae), a new cave-dwelling species from Lagoa Santa Karst, Southeastern Brazil. 14341 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 174524 records from Tasmanian Museum and Art Gallery provider for OZCAM. 353 records from Colección de Entomología - Arthropoda. 938 records from TTRS Mammals. 150 records from Museu Paraense Emílio Goeldi - Platyhelminthes Collection. 2 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 29 records from Contribution to the Ichneumoninae (Hymenoptera, Ichneumonidae) of Nepal. 2 records from Un nouveau genre et une nouvelle espèce de Cigale aphone du Malawi (Rhynchota, Cicadidae, Cicadettinae). 1 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 70 records from Base de datos de Rana catesbeiana.. 852 records from Estructura poblacional, variación genética y conservación de tres especies del género Pinus, endémicas de México. 20 records from New data on the taxonomy, distribution and host plants of Australian Epermeniidae (Lepidoptera: Epermenioidea). 3 records from A taxonomic revision of Globba subsect. Nudae (Zingiberaceae). 30 records from Uroptychus nitidus (A. Milne-Edwards, 1880) and related species (Crustacea: Decapoda: Anomura: Chirostylidae) from the western Atlantic. 1641 records from Consolidación y sistematización de las colecciones de referencia de peces y mamíferos marinos del ITESM Campus Guaymas. 15 records from Leafhopper subfamily Ledrinae of the Indian subcontinent: 1. Description of Yelahanka gen. nov. (Hemiptera: Cicadellidae) with seven new species and new combinations. 46 records from Occurrences of algae inhabiting the basidiocarps of wood-decaying Basidiomycetes in the Central Ural. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 2 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 17 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 1811 records from Inventario florístico de la Sierra de San Carlos, Tamaulipas. 4 records from Further information on Lolibaia Gorbunov & Gurko, 2017 (Lepidoptera: Sesiidae: Synanthedonini) with description of three new species from tropical Africa. 13 records from Pyura (Tunicata: Ascidiacea: Pyuridae) on the coasts of Panama. 853765 records from Museums Victoria provider for OZCAM. 17159 records from Duke University Herbarium Algae Collection. 6755 records from Plan de vertebrados de la Patagonia. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 5 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 59524 records from SysTax - Zoological Collections. 12869 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 1 records from A new amphibious troglobitic styloniscid from Brazil (Isopoda, Oniscidea, Synocheta). 8 records from Epimeria cleo sp. nov., a new crested amphipod from the Ross Sea, Antarctica, with notes on its phylogenetic affinities (Crustacea, Amphipoda, Eusiroidea, Epimeriidae). 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 1 records from A new species of nurse-frog (Aromobatidae, Allobates) from the Madeira River basin with a small geographic range. 11 records from Three new species of Thaloe Brescovit (Araneae: Anyphaenidae: Anyphaeninae), with descriptions of the first known females of the genus. 846 records from Sphaeriid clams. 318 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 42 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 243207 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 4 records from Gammaropsis elvirae sp. nov., a widely distributed amphipod (Amphipoda: Photidae) in the Yucatan Shelf, with ecological comments and a key for the genus in tropical America. 7 records from Four new cyclophoroid species from Thailand and Laos (Gastropoda: Caenogastropoda: Alycaeidae, Diplommatinidae, Pupinidae). 2 records from Review of lady beetles in the Cycloneda germainii species complex (Coleoptera; Coccinellidae: Coccinellinae: Coccinellini) with descriptions of new and unusual species from Chile and surrounding countries. 611 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 36 records from Universidad del Valle de Guatemala - Colecciones Biológicas - Equinodermos. 187 records from UWIZM Mammals. 43 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 6977 records from 2019_NSMK_PL_2. 2845 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Nematodos Chetumal). 4 records from Discovery of leaf-mining Tischeriidae (Lepidoptera) in Colombia and their distribution in the Neotropics. 6 records from Oxynoemacheilus kentritensis, a new species from the upper Tigris drainage in Turkey with remarks on O. frenatus (Teleostei: Nemacheilidae). 10 records from Cladistic analysis and description of a new species of the Brazilian genus Atlantodesmus Hoffman, 2000 (Diplopoda: Polydesmida: Chelodesmidae). 6468 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 30 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) IX. The maculosa species-group, with descriptions of eighteen new species. 2 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 1 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 5 records from Three new species of the spider genus Belisana Thorell, 1898 (Araneae: Pholcidae) from Xishuangbanna, Yunnan, China. 1156 records from Diversidad y conservación de orquídeas de la región de Chimalapa, Oaxaca, México. 4 records from Descriptions of three new species of Odonata from Brazil. 1 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 14288 records from Collection Pisces SMF. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 1 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 32 records from Three new species of Mesovelia Mulsant & Rey (Hemiptera: Heteroptera: Mesoveliidae) from India. 67 records from MEXU/Tipos de plantas vasculares. 3 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 30 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 2223 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (MZFC_OD). 2 records from A taxonomic synopsis of Chrysomydas Wilcox, Papavero & Pimentel (Diptera: Mydidae: Mydinae), with first bionomic records for the genus and description of a new species from Brazil. 4 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 7 records from Macropsini (Hemiptera: Cicadellidae) of Thailand, with description of two new species and three new country records. 9 records from New discoveries for the subfamily Phtisicinae Vassilenko, 1968 (Crustacea: Senticaudata) from the Brazilian coast. 1613 records from Biodiversidad asociada a mantos de rodolitos y praderas de pastos marinos en Bahía Concepción, BCS. 4 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 2 records from A new species of the porcelain crab genus Petrolisthes from the Pacific coast of Panama, with taxonomic notes on closely related species (Decapoda: Anomura Porcellanidae). 13 records from First record of Africactenus Hyatt, 1954 and redescriptions of two poorly known species of Ctenus Walckenaer, 1805 (Araneae, Ctenidae, Cteninae) from India. 14324 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 1 records from Review of Lecithoceridae (Lepidoptera: Gelechioidea) in the Oceanian Region, with description of a new species and a checklist of the family. 16 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 14645 records from SJRP herbarium - Universidade Estadual Paulista Júlio de Mesquita Filho - Herbário Virtual REFLORA. 19 records from Modelaje de la distribución potencial de 10 especies de anfibios y reptiles en riesgo de extinción con escasos registros de presencia (ANONAU). 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 2 records from Two new species of Dactylonotus Parent, 1934 (Diptera: Dolichopodidae) from South Africa and a key to Afrotropical species. 3 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 5 records from One new Pseudopoda species group (Araneae: Sparassidae) from Yunnan Province, China, with description of three new species. 9 records from Revision of Khoikhoiinae (Hymenoptera, Braconidae). 291 records from Native Bee Baseline and Effects Monitoring on the Green Mountain National Forest 2015. 1 records from A new genus and species of a terrestrial cavernicolan planarian from Barro Colorado Island, Panama (Platyhelminthes, Tricladida, Cavernicola). 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 9 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 6 records from Two new species of the genus Trilacuna from Chongqing Municipality, China (Araneae, Oonopidae). 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 37238 records from Herbarium Willing at Herbarium Berolinense, Berlin (B). 52 records from Description of three new velvet geckos (Diplodactylidae: Oedura) from inland eastern Australia, and redescription of Oedura monilis De Vis. 38383 records from Botanical Museum, Copenhagen, Mycology Herbarium. 40 records from Records of Giant Silkmoths (Saturniinae) from Vermont Collections and 2002-2007. 5 records from A new Candonopsini (Ostracoda) genus from subterranean waters of New South Wales (Australia). 4 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 197 records from TransForest - vegetation, lichen and fungi data 2016. 3 records from Otacilia fansipan spec. nov., the second congener recorded from Vietnam (Arachnida: Araneae: Phrurolithidae). 126 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 2 records from A remarkable new plant bug genus and species (Hemiptera, Heteroptera, Miridae, Deraocorinae) from the Australian wet tropics. 11 records from Revision of Aciuroides Hendel and Neoacanthoneura Hendel (Diptera: Ulidiidae: Pterocallini). 5 records from Rhinogobius houheensis, a new species of freshwater goby (Teleostei: Gobiidae) from the Houhe National Nature Reserve, Hubei province, China. 1 records from New Antarctic stenothoids sensu lato (Amphipoda, Crustacea). 1 records from Gymnesigobius medits (Teleostei: Gobiidae), a new gobiid genus and species from the western Mediterranean slope bottoms. 3137 records from Salvatore S. Anzaldo Collection. 1871 records from NMU Mammal Collection (Arctos). 1198 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Peces). 14 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 3 records from Species diversity of Rhinebothrium Linton, 1890 (Eucestoda: Rhinebothriidea) from Styracura (Myliobatiformes: Potamotrygonidae), including the description of a new species. 8 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 3 records from A new genus and species of Sclerodactylidae (Echinodermata: Holothuroidea: Sclerothyoninae) from the Pacific coast of Panama, and assignment of Neopentamera anexigua to Sclerothyoninae. 1 records from A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar. 74 records from Reptiles de la expedición al Río Apaporis - Proyecto Colombia BIO. 32 records from A new tanaidacean subfamily, Bathytanaidinae (Crustacea: Paratanaididae), from the Australian continental shelf and slope. 24 records from The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae). 22 records from Contributions to the study of the grasshopper (Orthoptera: Acrididae Gomphocerinae) courtship songs from Kazakhstan and adjacent territories. 85 records from The Crematogaster (Hymenoptera, Formicidae, Myrmicinae) of Costa Rica.. 165 records from CMNH Mammals. 170 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 1244 records from Amphibian and reptile species occurrences in the Tana River Basin, Kenya, digitized from preserved specimens at the National Museums of Kenya. 1 records from Afroanomalia pseudoclistopyga, a new genus and species of pimpline parasitoid wasp (Hymenoptera: Ichneumonidae: Pimplinae) from the Afrotropical region. 1 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 2 records from Macrozoque hoplandrioides (Coleoptera: Staphylinidae: Aleocharinae), a new genus and species of false Lomechusini from México. 9012 records from URM - Herbário Pe. Camille Torrand. 25 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 16 records from Three new species of earthworms belonging to the genera Amynthas and Metaphire (Oligochaeta: Megascolecidae) from Yunnanı China. 1 records from Species of Wadicosa (Araneae, Lycosidae): a new species close to W. quadrifera (Gravely) from the Western Ghats, India. 11679 records from ZMMU MSU, White Sea Branch. 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 1 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 16 records from Review of the Poecilimon (Poecilimon) zonatus species group and description of new species from Turkey with data on bioacoustics and morphology (Orthoptera: Phaneropterinae). 3 records from A revision of the New Zealand weevil genus Irenimus Pascoe, 1876 (Coleoptera: Curculionidae: Entiminae). 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 8 records from Four new species of Diptilomiopinae from China (Acari: Eriophyoidea: Diptilomiopidae). 61 records from GH herbarium - Harvard University Herbarium - Herbário Virtual Reflora. 236 records from Rotifers of Macquarie Island. 3 records from The genus Thelepus Leuckart, 1849 (Annelida, Thelepodidae) in Brazil, with a redescription of the holotype of T. setosus (Quatrefages, 1866). 1 records from Rediscovery of Terebratulina austroamericana Zezina, 1981 (Brachiopoda: Cancellothyrididae) from off northern Chile. 1 records from A new diminutive sisorid catfish (Actinopterygii: Siluriformes) from northeastern India. 1293 records from Flora genérica de las gramíneas del estado de Tlaxcala. 69 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 10 records from Three species of Reteporella (Bryozoa: Cheilostomata) in a diapiric and mud volcano field of the Gulf of Cádiz, with the description of Reteporella victori n. sp. 27 records from Revisionary systematics of the endemic soft coral fauna (Octocorallia: Alcyonacea: Alcyoniina) of the Agulhas Bioregion, South Africa. 5 records from Halanonchus scintillatulus sp. nov. from New Zealand and a review of the suborder Trefusiina (Nematoda: Enoplida). 4 records from Additional knowledge respecting taxonomy of the social wasp genus Ropalidia (Hymenoptera: Vespidae: Polistinae) from Vietnam, with new records of three species and an updated key to species. 1503 records from ZUEC-ARA - Coleção de Aracnideos do Museu de Zoologia da UNICAMP. 1 records from A new species and southernmost record of Cestrus Townes (Hymenoptera Ichneumonidae, Cryptinae). 6037 records from PACA-AGP - Herbarium Anchieta. 2 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 4 records from New records of phytoseiid mites from Mauritius Island (Acari: Mesostigmata. 4 records from The ant genus Tetraponera in the Afrotropical region: the T. grandidieri group (Hymenoptera: Formicidae).. 5464 records from Natural History Museum Maastricht (NL) - Herbarium. 742 records from Colección Hidrobiológica del Museo de Historia Natural de la Universidad Industrial de Santander. 2 records from A new genus Microsarimodes with one species from Hainan Province in China (Hemiptera: Fulgoromorpha: Issidae). 2 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. IV. Alopoglossidae, Gymnophthalmidae. 9384 records from MZL Invertebrate Collections. 1 records from Taxonomy of the ant genus Nesomyrmex Wheeler (Formicidae, Myrmicinae) in the Afrotropical region, with a review of current species groups and description of a new species of the N. angulatus group from Mozambique. 2 records from Redescription and taxonomic notes on Cyclops bohater Koźmiński, 1933 and Cyclops lacustris G. O. Sars, 1863 (Arthropoda, Crustacea), with an identification key to the Cyclops species of Fenno-Scandinavia. 1 records from New look on the geographical variation in Rhinolophus clivosus with description of a new horseshoe bat species from Cyrenaica, Libya. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 9 records from A new species of Hersiliola Thorell, 1870 (Araneae, Hersiliidae) from Turkey. 4 records from Four new species of Xiphocentron Brauer, 1870 (Trichoptera: Xiphocentronidae) from the Atlantic Forest, southeastern Brazil. 8193 records from Invertebrates of the river Tana Basin in Kenya available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section. 139 records from Species of Cerambycinae (Insecta, Coleoptera, Cerambycidae) from east Paraná State (Brazil), with new geographic records. 13940 records from Collection of Coleoptera. 11 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 5 records from A new species of Pherbellia (Diptera: Sciomyzidae) from Iran. 2 records from Redescription of Stilobezzia (Stilobezzia) albicoxa Lane & Forattini, 1956 with new synonymy (Diptera: Ceratopogonidae). 8496 records from Vascular Plants Collection of National Museum of Nature and Science. 4268 records from Free-living marine Nematodes from Ali, Rada Tilly and El Limite sandy beaches (Chubut, Argentina) 2006.. 37 records from Revision of New World Cosmorrhyncha Meyrick, 1913 (Lepidoptera: Tortricidae: Olethreutinae), with descriptions of five new species. 2 records from Unveiling the morphology of the Oriental rare monotypic ant genus Opamyrma YAMANE, BUI & EGUCHI, 2008 (Hymenoptera: Formicidae: Leptanillinae) and its evolutionary implications, with first descriptions of the male, larva, tentorium, and sting apparatus. 1374 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 17698 records from List of the specimens of the Vanuatu National Herbarium (PVNH). 10 records from Taxonomic notes on Alpheus inopinatus Holthuis & Gottlieb, 1958 and Alpheus cf lobidens De Haan, 1849 from Kuwait (Malacostraca: Decapoda: Alpheidae). 12 records from New species of Peckhamia Simon, 1900 (Salticidae: Dendryphantini: Synagelina) from the Greater Antilles. 5 records from The InBIO Barcoding Initiative Database: DNA Barcoding reveals sexual dimorphism in Isotrias penedana Trematerra, 2013 (Lepidoptera: Tortricidae, Chlidanotinae). 973 records from Zambian Bat Collections Worldwide. 2483 records from Inventario florístico y base de datos de la familia Cucurbitaceae en México. 7 records from One new species and two redescriptions of Marphysa (Eunicidae, Annelida) species of the Aenea-group from Australia. 1 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 14 records from A new freshwater shrimp species of the genus Palaemon Weber, 1795 (Decapoda: Caridea: Palaemonidae) from northeastern Japan. 3 records from A new species of the armored spider genus Caraimatta Lehtinen, 1981 from Colombia (Araneae: Synspermiata: Tetrablemmidae). 48 records from Poliquetos litorales de la región norte y centro del estado de Veracruz. 277 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 2 records from Two new species of Yaginumaella (Araneae, Salticidae) from Wuling Mountain, China. 77735 records from Coleoptera collection, NHM. 1 records from Neocrassocoris, a new apterous genus of Carventinae from China (Heteroptera: Aradidae). 4 records from A new species of the greeneye genus Chlorophthalmus (Teleostei: Chlorophthalmidae) from the central North Pacific. 497 records from Artsprosjektet 43-15, Norway's hidden marine biodiversity: The hunt for cryptic species within the coralline algae. 3 records from Campydoroides manautei gen. et sp. nov. from New Caledonia and a reappraisal of the suborder Campydorina (Nematoda). 6 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 264 records from Swedish Malaise Trap Project (SMTP) - Mycetophilidae, Keroplatidae. 2 records from More cautionary tales: family, generic and species synonymies of recently published taxa of ghost and mud shrimps (Decapoda: Axiidea and Gebiidea). 67 records from Standardized Bumble bee (Bombus) Surveys Conducted in Vermont in 2019. 562 records from UWIZM International Lepidoptera Collection. 1 records from A new species of Conognatha Eschscholtz, 1829 (Coleoptera: Buprestidae), with new state records of the genus for Brazil. 14 records from Distribution of the genus Larinia in the Maghreb, with the first record of Larinia chloris in Algeria (Araneae: Araneidae). 2 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Heilongjiang, China. 3 records from A new species of the genus Tshurtshurnella Kusnezov, 1927 (Hemiptera Fulgoromorpha: Issidae) from Turkey. 151 records from Helmintos parásitos de peces del sureste de México. 2 records from Cnemaspis rajakarunai sp. nov., a rock dwelling day-gecko (Sauria: Gekkonidae: Cnemaspis) from Salgala, an unprotected lowland rainforest in Sri Lanka. 3 records from A new species of Neobathyclupea from the northern Indian Ocean with comments on N. malayana (Teleostei, Perciformes, Bathyclupeidae). 8 records from Lepidepecreoides stoddartae sp. nov. from the Falkland Islands (Amphipoda: Tryphosidae). 234 records from Mosses and Lichens (Vermorel coll.). 15 records from New species and new records of gelechiid moths (Lepidoptera, Gelechiidae) from southern Siberia. 1 records from Two new species of Plutomurus Yosii (Collembola, Tomoceridae) from the Caucasus. 4 records from Two new deep-sea species of Laonice (Annelida: Spionidae) from the Mediterranean Sea. 3 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 3 records from New species of Poecilocloeus Bruner, 1910 (Orthoptera: Acrididae: Proctolabinae) from Paraná State, Brazil. 7 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 2 records from Revision of the genus Systellapha Enderlein (Micropezidae, Taeniapterinae). 10 records from Ten new species of the spider genus Pholcus Walckenaer, 1805 (Araneae, Pholcidae) from Southeast Asia. 86 records from UWIZM Cnidarians. 15 records from Collections de coquilles continentales du Muséum d'histoire naturelle de Grenoble. 4998 records from Les spermaphytes de l'Herbier du Centre National de Floristique de Côte d'Ivoire: quatrième partie.. 3 records from Distributional and taxonomic notes on the crab spider genus Talaus Simon, 1886 with description of a new species (Araneae: Thomisidae). 24 records from Sistemática molecular de Trogoniformes (Aves): Filogenia del orden y análisis de variabilidad genética de quetzales en la reserva de la Biosfera El Triunfo. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 195 records from Aportación al conocimiento de la fauna de Ascidias del litoral Pacífico de México. 604 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 3 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 3446 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 14744 records from Swiss National Grasshoppers Databank. 293 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 16 records from Revalidation of Acanthinozodium Denis, 1966 with description of three new species and discovery of a remarkable male palpal character (Araneae, Zodariidae). 70427 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 35150 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 139 records from Annotated checklist of bats (Mammalia: Chiroptera) of Mount Cameroon, southwestern Cameroon. 441 records from Estado actual del conocimiento biológico de algunas especies de roedores de las familias Muridae, Geomyidae, Heteromyidae y Sciuridae (Rodentia: Mammalia) incluidas en el PROY-NOM-059-ECOL-2000. 36 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 2 records from Multivariate discrimination and description of a new species of Tapinoma from the Western United States.. 4 records from Description of a new species of deep-water snake eel, Ophichthus mccoskeri (Ophichthidae: Ophichthinae) from Andaman Sea, India. 2 records from New records of brittle stars (Echinodermata: Ophiuroidea) from the Lakshadweep atolls, northern Indian Ocean, with notes on Indophioderma ganapatii Sastry Marimuthu & Rajan, 2019. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 11 records from Tokunagaia Saether from China (Diptera: Chironomidae: Orthocladiinae). 1 records from A new species of Pyrrhosphodrus (Hemiptera: Heteroptera: Reduviidae) from the Caatinga ecosystem in Brazil, with notes on the genus. 20897 records from Michigan State University Herbarium Lichens. 39 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 4 records from Review of Eotrogaspidia Lelej (Hymenoptera: Mutillidae: Trogaspidiini). 1 records from Limbodessus skalei sp. nov., a new diving beetle species from the west Papuan Archipelago (Coleoptera: Dytiscidae, Bidessini). 4 records from Thorectinae (Porifera: Demospongiae: Dictyoceratida) from Northeastern Brazil: two new species and transfer of Scalarispongia cincta (Boury-Esnault, 1973) to the genus Thorecta Lendenfeld, 1888. 60 records from Wichita State University Collection. 147 records from Evaluación de la resistencia a la roya (Uromyces appendiculatus) en poblaciones silvestres y cultivadas de frijol, mediante el empleo de marcadores genéticos moleculares. 56 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) (Peces). 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 2 records from A new species and new records of Malagasy Megalopinus Eichelbaum (Coleoptera Staphylinidae, Megalopsidiinae), with notes on the sperm pump in rove beetles. 163 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México (Teocintle). 10 records from Four new species of the spider genus Cicurina Menge, 1871 from China (Araneae: Dictynidae). 10 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 2 records from A new species of Gamasellodes Athias-Henriot (Mesostigmata: Ascidae) from Brazil and a key to the world species of the genus. 327 records from pbzt_insect_biodiversity. 2 records from Eudraces barclayi sp. nov., with some notes on the genus Eudraces Marshall (Coleoptera: Curculionidae: Entiminae: Myorhinini). 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 253 records from NZCS Upper Tapanahony Expedition 1991. 1 records from Calidolipeurus, new genus for Lipeurus megalops Piaget, 1880 (Phthiraptera: Ischnocera: Oxylipeurus-complex), with a redescription of the type species and a preliminary key to the Oxylipeurus-complex. 4 records from Three new species and one new record of Torrenticolidae (Acari, Hydrachnidia) from Wuyishan with an updated key for Chinese fauna. 22 records from Tanzanian Vertebrate Collection. 3 records from A new Central American genus of pleasing fungus beetles (Coleoptera: Erotylidae) from the Ischyrus-Megischyrus complex. 2 records from Ovomanonychus, a new genus of South American Sericoidini (Coleoptera Scarabaeidae: Melolonthinae). 12 records from New Psocoptera (Hexapoda, Insecta) records from Belarus. 31 records from Three new widely distributed and polymorphic species of Amynthas earthworms (Oligochaeta, Clitellata, Megascolecidae) from South China. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 2 records from Morphology and infraciliature of two new earthworm ciliates, Hoplitophrya polymorphus sp. nov. and Anoplophrya simplex sp. nov. (Ciliophora: Oligohymenophorea: Astomatia). 3 records from Afrotropical Asilidae (Diptera) 18. The genus Smeryngolaphria Hermann, 1912 (Laphriinae). 105 records from Rainforest and cloud forest Scolytodes (Curculionidae, Scolytinae, Hexacolini) from the Arthropods of La Selva inventory in Costa Rica: new species, new synonymy, new records. 12 records from An ancient radiation: Ortholasmatine harvestmen in A
Keywords: GBIF; biodiversity; species occurrences